Foam Compositions, Foam Padded Materials, and Packaging Articles

JP2024508229A5Inactive Publication Date: 2025-02-073M INNOVATIVE PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023546164
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-31
Filing Date
2022-02-01
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing packaging materials, such as closed cell extruded polystyrene foam and bubble wrap, are not renewable or compostable, leading to significant landfill waste and have low recycling rates compared to paper-based products, despite offering effective thermal insulation and impact protection.

Method used

Development of polymeric foam compositions that form a foam structure with a hollow interior and porous outer shell, which can be made from renewable materials and are compostable, providing cushioning and recyclability similar to traditional packaging materials.

Benefits of technology

The new foam compositions offer renewable, compostable, and recyclable packaging solutions with comparable protective properties to traditional materials, reducing environmental impact by minimizing waste and improving recycling rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Disclosed are polymeric foam compositions, foam-padded materials comprising such polymeric foam compositions disposed on a sheet material, and packaging articles (e.g., envelopes) made from such foam-padded materials. The polymeric foam composition on the sheet material has a plurality of foam structures formed from the foamable composition, the foam structures being attached to the sheet material by a layer of the foamable composition, each having a hollow core and a foam exterior shell.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Existing packaging (e.g., shipping envelopes) come in two general forms, with and without a cushioning layer. Cushioning is an important component of protective packaging. It is known to use closed-cell extruded polystyrene foam or bubble wrapping, such as that available under the trade name "BUBBLE WRAP", as a cushioning component in packaging. Such materials cannot be renewable or compostable. Thus, most end up in landfills. Even when they are renewable, it is well-established that plastic products are recycled at a much lower rate than paper-based products. More environmentally friendly approaches to making packaging have been attempted based on cellulosic materials and water-based adhesives, but such packaging materials may not be durable enough to provide suitable properties (e.g., effective insulation, impact protection, and compression resistance). Summary of the Invention

[0002] The present disclosure provides polymeric foam compositions, foam padded materials comprising such polymeric foam compositions, and packaging articles (eg, envelopes) comprising such foam padded materials.

[0003] In one embodiment, a foam composition is provided that includes a polymer component on a sheet material, which polymer component forms a foam structure with a hollow interior and a foamed porous outer shell. These materials can be renewable and / or compostable when using appropriate material sections for the sheet material and foam composition. These foam sheet materials can have a mechanical structure very similar to "BUBBLE WRAP" with the advantage of being easier to recycle and / or compost.

[0004] In another embodiment, there is provided a renewable and / or compostable foam padded material comprising: a sheet material having first and second major surfaces, the sheet material comprising a renewable material (e.g., paper); and a polymeric component forming a plurality of foam structures, each having a hollow interior and having a foamed porous outer shell disposed on the first major surface of the sheet material, wherein the foam composition is as described herein.

[0005] In another embodiment, an optional reusable and / or compostable foam padded material is provided that includes a sheet material having first and second major surfaces, and a foam composition disposed on the first and second major surfaces of the sheet material, the foam composition forming a plurality of foam structures each having a hollow interior and having a foamed porous outer shell.

[0006] In yet another embodiment, a packaging article is provided comprising: a first wall having a first inner surface and a first outer surface opposite the first inner surface; a second wall having a second inner surface and a second outer surface opposite the second inner surface, the first and second inner surfaces defining an interior of the packaging article and the first and second outer surfaces defining an exterior of the packaging article; a foam composition disposed on at least a portion of each of the first and second inner surfaces; and a seal joint at one or more edges of the first and second walls, the seal joint comprising the foam composition and attaching the first wall to the second wall, wherein the first and second walls can comprise renewable materials, and the foam composition is as described herein.

[0007] In yet another embodiment, a packaging article is provided comprising: a first wall having a first inner surface and a first outer surface opposite the first inner surface; and a second wall having a second inner surface and a second outer surface opposite the second inner surface, the first and second inner surfaces defining an interior of the packaging article and the first and second outer surfaces defining an exterior of the packaging article, the first wall and the second wall each comprising first and second sheet materials facing each other, wherein a foam composition described herein is disposed between the first sheet material and the second sheet material.

[0008] In yet another embodiment, a packaging article is provided comprising: a first wall having a first inner surface and a first outer surface opposite the first inner surface; a second wall having a second inner surface and a second outer surface opposite the second inner surface, wherein the first and second inner surfaces define an interior of the packaging article and the first and second outer surfaces define an exterior of the packaging article; a foam composition disposed on at least a portion of each of the first and second inner surfaces; and a seal joint at one or more edges of the first and second walls, the seal joint comprising the foam composition and attaching the first wall to the second wall, wherein the first and second walls comprise renewable materials, and the foam composition is as described herein.

[0009] In yet another embodiment, there is a sheet material having a first side and an opposing second side, and a foam composition described herein is disposed on both the first side and the second side, hi some embodiments, the foam composition comprises a plurality of foam structures, each having a hollow interior and each having a foamed porous outer shell.

[0010] In yet another embodiment, the packaging article contains a foam composition disposed in a discrete pattern on at least a portion of each of the first and second interior surfaces, with the areas not containing the foam composition covering 20%, 30%, 40%, 50%, 60%, 80%, 90%, and 95% of the interior surfaces. For example, there may be no foam present in flaps and / or folded areas of the structure.

[0011] In yet another embodiment, there is a packaging material having a first sheet material and a plurality of foam structures formed from a foamable composition, the plurality of foam structures being attached to the sheet material by a layer of the foamable composition, each having a hollow core and a foam exterior shell, where the total porosity of the plurality of foam structures is determined by adding the hollow core volume to the exterior shell void volume by X-ray microtomography, then dividing the sum by the foam structure volume and multiplying by 100, the total porosity being greater than 50% and less than 100%. This embodiment is made by rotogravure printing the foamable composition onto a sheet material, the foamable composition being attached to the sheet material by a layer of the foamable composition, and then drying the foamable composition to foam into a foam structure having a hollow core and a foam exterior shell, as best seen in Figures 18 and 19.

[0012] Certain terms in this disclosure are defined below. Other terms are familiar to those of skill in the art and are intended to be given the meanings that those skilled in the art have assigned to them.

[0013] The terms "polymer" and "polymeric material" include, but are not limited to, organic homopolymers, copolymers, such as block copolymers, graft copolymers, random copolymers, and copolymers, terpolymers, and the like, as well as blends and modifications thereof. Furthermore, unless otherwise specifically limited, the term "polymer" is intended to encompass all possible geometric configurations of the material. These configurations include, but are not limited to, isotactic, syndiotactic, and atactic symmetries.

[0014] The term "copolymer" refers to a polymer that contains two or more different monomeric units or segments, including terpolymers, tetrapolymers, and the like.

[0015] The term "compostable" refers to a material, composition, or article that meets the standard ASTM D6400 or ASTM D6868. It should be noted that since these two standards are applicable to different types of materials, a material, composition, or article will usually only meet one of them, the most applicable one, in order to be "compostable" as defined herein. In certain embodiments, the term "compostable" preferably refers to a material, composition, or article that meets the standard ASTM D6400. In particular, a compostable material, composition, or article also meets the ASTM D5338 standard. In particular, a compostable material, composition, or article also meets one or more of the standards EN 13432, AS 4736, AS 5810, or ISO 17088. More particularly, a compostable material, composition, or article also meets the ISO 14855 standard.

[0016] It should be noted that the term "compostable" as used herein is not interchangeable with the term "biodegradable." Something that is "compostable" should degrade within the time specified by the above standards into a material that has toxicity, particularly phytotoxicity, consistent with the above standards. The term "biodegradable" does not specify the time that a material should degrade, nor does it specify that the compound that degrades pass any standard for lack of toxicity or environmental harm. For example, a material that meets the ASTM D6400 standard should pass tests specified in ISO 17088, which addresses the "presence of high levels of regulated metals and other harmful components," while a material that is "biodegradable" may have any level of harmful components.

[0017] The term "recyclable" refers to a material, composition, or article that meets at least one of the following standards: the Voluntary Standard for Repulping and Recycling Corrugated Fiberboard published by the Fibre Box Association (FBA) part 1 (repulpability), the Voluntary Standard for Repulping and Recycling Corrugated Fiberboard published by the Fibre Box Association (FBA) part 2 (recyclability), and the ISO 18601 standard. Certain renewable items meet the Repulping and Recycling Corrugated Fiberboard part 1 (repulpability). Certain renewable items meet the Voluntary Standard for Repulping and Recycling Corrugated Fiberboard part 2 (recyclability). Further, certain renewable items meet the Voluntary Standard for Repulping and Recycling Corrugated Fiberboard part 1 (repulpability) and part 2 (recyclability). Even more specifically, the renewable items meet the Voluntary Standard for Repulping and Recycling Corrugated Fiberboard part 1 (repulpability) and part 2 (renewability) standards, as well as the ISO 18601 standard. Even more specifically, the renewable items further meet the ISO 18604:2013 standard. All references to the Voluntary Standard for Repulping and Recycling Corrugated Fiberboard standard, whether to part 1, part 2, or both, refer to the 2013 version of the standard. It should be noted that renewable materials may include materials, such as adhesives, that do not meet one or more of the above standards.This is because materials, particularly adhesives, are typically removed from paper products during the recycling process. Such materials, particularly adhesives, that are not themselves renewable but are easily removed from the product during the recycling process are referred to herein as "recyclable." Thus, a "recyclable" article may contain components that are renewable as well as components that are compatible with recycling.

[0018] Throughout this disclosure, the singular forms "a," "an," and "the" are often used for convenience, but are intended to include the plural unless expressly stated in the singular or clearly indicated by the context. When referring to the singular only, the term "one and only one" is typically used.

[0019] The term biodegradable refers to materials that decompose by aerobic biodegradation in the presence of soil microorganisms as defined by ASTM D5988-18, or by aerobic biodegradation under controlled composting conditions as defined by ASTM 5338-15, or by anaerobic biodegradation under high solids anaerobic digestion conditions such as in treatment centers for municipal waste, biologically active landfills, and the like as defined by ASTM D5511-18.

[0020] Terms indicating frequency, such as (but not limited to) "common," "typical," and "ordinary," are used herein to refer to features that are frequently used in this disclosure, and are not intended to imply that the features are present in the prior art, much less that they are common, ordinary, or typical in the prior art, unless specifically used with reference to the prior art.

[0021] As used herein, the term "comprising" and variations thereof do not have a limiting meaning when these terms appear in the specification and claims. Such terms are understood to imply the inclusion of the described step or element or group of steps or elements, but not the exclusion of any other step or element or group of steps or elements. "Consisting of" means to include and be limited to everything before the phrase "consisting of". Thus, the phrase "consisting of" indicates that the recited elements are necessary or mandatory, and that no other elements may be present. "Consisting essentially of" means to include everything before the phrase, and is limited to other elements that do not interfere with or contribute to the activity or action specified in this disclosure with respect to those recited elements. Thus, the phrase "consisting essentially of" indicates that the recited elements are necessary or mandatory, but that other elements are optional and may or may not be present depending on whether they substantially affect the activity or action of the recited elements. Any element or combination of elements described herein with open-ended language (e.g., "comprising" and its derivatives) is considered to be further described with closed-ended language (e.g., "consisting of" and its derivatives) and partially closed-ended language (e.g., "consisting essentially of" and its derivatives).

[0022] The words "preferred" and "preferably" refer to embodiments of the present disclosure that may provide certain benefits, under particular circumstances. However, other claims may also be preferred, under the same or other circumstances. Moreover, the recitation of one or more preferred claims does not imply that other claims are not useful, and is not intended to exclude other claims from the scope of the present disclosure.

[0023] As used herein, the term "or" is generally used in its ordinary sense, including "and / or," unless the content specifically dictates otherwise. The term "and / or" refers to one or all of the listed elements or a combination of any two or more of the listed elements.

[0024] Further, all numbers herein are deemed to be modified by the term "about," and in certain embodiments, preferably, by the term "exactly." As used herein, in the context of a measured quantity, the term "about" refers to the variation in the measured quantity as would be expected by one of ordinary skill in the art making the measurement and exercising a level of care commensurate with the purpose of the measurement and the precision of the measuring device used. As used herein, a "up to" number (e.g., up to 50) is inclusive of that number (e.g., 50).

[0025] Also herein, the recitation of numerical ranges by endpoints includes all numbers subsumed within that range and those endpoints (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.). Also, when several lower limits of a variable are listed consecutively and several upper limits of the same variable are listed consecutively, the range of that variable between any selected lower limit and any selected upper limit is within the scope of the disclosure.

[0026] The terms "in the range" or "within a range" (and similar descriptions) include the endpoints of the stated range.

[0027] Groupings of alternative elements or embodiments disclosed herein should not be construed as limitations. Each group member may be referred to and claimed individually or in any combination with other members of the group or other elements found in the group. It is anticipated that one or more members of a group may be included in or deleted from a group for reasons of convenience and / or patentability. When any such inclusion or deletion occurs, the specification is deemed herein to include the modified group and thus implements the full recitation of all Markush groups used in the appended claims.

[0028] References throughout this specification to "one embodiment," "an embodiment," "certain embodiment," or "some embodiments" mean that the particular features, configurations, compositions, or characteristics described with respect to the embodiment are included in at least one embodiment of the present invention. Thus, the appearances of such phrases in various places throughout this specification are not necessarily referring to the same embodiment of the present invention. Moreover, the particular features, configurations, compositions, or characteristics may be combined in any suitable manner in one or more embodiments.

[0029] The above "Summary of the Invention" of this disclosure is not intended to describe each disclosed embodiment or every implementation of the present invention. The following description more specifically illustrates exemplary embodiments. In several places throughout this application, guidance is provided through the enumeration of examples, which can be used in various combinations. In each instance, the recited items serve only as a representative group and should not be construed as an exclusive enumeration. Thus, the scope of the disclosure should not be limited to the specific exemplary structures described herein, but extends to at least the structures described by the language of the claims, and equivalents of these structures. Any elements expressly described herein as alternatives may be expressly included in or excluded from the claims in any combination as desired. Various theories and possible mechanisms may be discussed herein, but in no event should such discussion be construed as limiting the claimed subject matter. [Brief description of the drawings]

[0030] [Figure 1A] 1 is a photograph of an exemplary foam padded material. [Figure 1B] 1 is a photograph of an exemplary foam padded material. [Figure 1C] 1 is a photograph of an exemplary foam padded material. [Figure 1D] 1 is a photograph of an exemplary foam padded material. [Figure 1E] 1 is a photograph of an exemplary foam padded material. [Figure 1F] 1 is a photograph of an exemplary foam padded material. [Figure 1G] 1 is a photograph of an exemplary foam padded material. [Diagram 2] 1 is a schematic diagram of an exemplary packaging article. [Diagram 3] FIG. 2 is a schematic diagram of another exemplary packaging article. [Figure 4] FIG. 2 is a schematic diagram of yet another exemplary packaging article. [Diagram 5]FIG. 2 is a schematic diagram of yet another exemplary packaging article having a flap in an open configuration (5). [Figure 6] FIG. 2 is a schematic diagram of yet another exemplary packaging article having flaps in a closed configuration (6). [Figure 7A] 2 is a schematic diagram of another exemplary packaging article having an adhesive portion. [Figure 7B] FIG. 13 is a schematic diagram of yet another exemplary packaging article having two adhesive portions on the flap. [Figure 8A] 1 is a photograph of an exemplary packaged article. [Figure 8B] 1 is a photograph of an exemplary packaged article. [Figure 9] 1 is a schematic diagram of an unwind station, a rotogravure station, an oven, and a winder. [Figure 10A] 1 is a schematic diagram of an exemplary packaging article. [Figure 10B] 1 is a schematic diagram of an exemplary packaging article. [Figure 10C] 1 is a schematic diagram of an exemplary packaging article. [Figure 11] A 3D printed rotogravure roll with a pattern on its surface. [Figure 12A] FIG. 2 is a schematic diagram of another packaging article. [Figure 12B] FIG. 2 is a schematic diagram of another packaging article. [Figure 13] FIG. 1 is a schematic diagram of a 3D printed rotogravure roll. [Figure 14] FIG. 1 shows the rotogravure cell dimension, which is the diameter d1 of the inscribed circle tangent to the sides of the hexagon drawn by connecting the centers of the individual cells in the rotogravure array. [Figure 15] FIG. 1 is a top view of one embodiment of the present invention having a foaming composition that forms a plurality of foam cells in a patterned array attached to a substrate. [Figure 16] FIG. 16 is a cross-sectional view of the embodiment of FIG. 15, showing that each foam cell includes an outer shell of foam composition and a hollow interior filled with air. [Figure 17]FIG. 17 is a schematic diagram of a mailer made from the embodiment of FIG. 16 having heat sealed seams, where the foam bubbles are compressed and heat sealed together to form a pouch having an interior with a cushioning array of foam bubbles. [Figure 18] 1 is an optical micrograph of a cross-section of foamed cells on a substrate, each foamed cell having an outer shell of foam composition and a hollow interior filled with air. [Figure 19] 1 is an image using X-ray tomography showing the porous outer shell of the foamed bubbles on a substrate and the inner hollow core of the foamed bubbles. [Figure 20] 1 shows the exterior of a rotogravure printing roll for applying a foaming composition to a substrate in a rectangular pattern with diagonal orientation. [Figure 21] 1 shows a patterned sheet having coated and uncoated areas on a substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] The present disclosure provides a polymer foam composition. The foam composition includes polymer components that form a plurality of foam structures on a sheet material. The foam structures can have a hollow interior and a foam exterior shell, as best seen in Figures 18 and 19.

[0032] Such polymer foam compositions can be used in renewable and / or compostable foam, and / or biodegradable padded materials and packaging articles (e.g., envelopes). The foam padded materials include a sheet material 10 having a first major surface 12 and a second major surface 14 opposite the first major surface, the sheet material optionally including a renewable material and a foam composition 16 described herein disposed on the first major surface and / or the second major surface of the sheet material.

[0033] Briefly, the packaging article includes a first wall having a first inner surface and a first outer surface opposite the first inner surface, and a second wall having a second inner surface and a second outer surface opposite the second inner surface. The first and second inner surfaces define the interior of the packaging article, and the first and second outer surfaces define the exterior of the packaging article. The packaging article has one or more edges where the first wall is attached to the second wall at a seal joint. Optionally, the article may have at least one opening where the first wall is not attached to the second wall, which is not required since it is possible to form the packaging article around an object that is placed inside the packaging article, thereby eliminating the need for an article with an opening. The foam composition described herein is disposed on at least a portion of each of the first and second inner surfaces. Preferably, the foam composition also forms a seal joint, thereby attaching the first wall of the packaging article to the second wall.

[0034] In certain embodiments, the polymer foam composition, foam padded material, or packaging article is renewable. In certain embodiments, the polymer foam composition, foam padded material, or packaging article is compostable. In certain embodiments, the polymer foam composition, foam padded material, or packaging article is biodegradable. In certain embodiments, the polymer foam composition, foam padded material, or packaging article are both renewable and / or compostable and / or biodegradable.

[0035] Foaming Composition The foamed composition is an organic polymer foam, i.e., a composite of a polymer matrix (i.e., polymeric component) and a gas dispersed therein, typically in bubbles or cells. During foam volume expansion, the gas phase is initially dispersed in the continuous polymer phase. Polymer foams can be prepared mechanically (e.g., by air dispersion, frothing), physically (e.g., by gas injection, bead foaming, expandable microspheres), or chemically (e.g., by using blowing agents that generate effective gas by pyrolysis or solvent evaporation).

[0036] Such foam compositions typically comprise closed cell foams, although open cell foams are also possible, In certain embodiments, the foam comprises closed cells, and optionally has open and / or burst cells.

[0037] The foam composition of the present disclosure can be water-soluble, and preferably at least partially water-soluble. In the context of a foam (i.e., a foam composition), an at least partially water-soluble foam means that at least 50% of the foam dissolves in water at 130°F (54°C) according to the Water Solubility Test described in the Examples section. In certain embodiments, at least 60%, at least 70%, at least 80%, at least 85%, at least 90%, at least 95% of the foam (i.e., the foam composition) dissolves in water at 130°F (54°C) according to the Water Solubility Test described in the Examples section. Such foam compositions include water-soluble components, such as one or more polymers, and one or more optional water-soluble additives, at room temperature or at elevated temperatures, as described in more detail below.

[0038] The foam compositions (i.e., foams) of the present disclosure are preferably heat sealable. This means that the foam composition is sufficiently thermoplastic and will liquefy and flow when exposed to thermal energy, mechanical energy, or a combination thereof (e.g., heat sealing, sonic welding), and will resolidify when cooled, thereby providing a seal between two substrate materials having the foam composition disposed therebetween. The sealability of the foam composition can be quantified using the seam strength test described in the Examples section. In certain embodiments, the foam compositions of the present disclosure have a seam strength of at least 1.0 lbs / in, at least 2.0 lbs / in, or at least 4.5 lbs / in.

[0039] In certain embodiments, the foam composition is biodegradable. This means that the internal integrity of the foam is at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95% or more, as demonstrated by the shedding or adhesion of the foam to paper, the ability of the foam to absorb shock, and the ability of the foam to withstand compression, the adhesion of the foam to the substrate. The durability of the foam composition can be quantified by the abrasion resistance test method in the examples.

[0040] In certain embodiments, the foam compositions of the present disclosure have a foam shedding mass loss from the Taber Abrasion Test described herein of 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less after abrasion according to the Abrasion Resistance Test described herein.

[0041] In certain embodiments, the polymer component of the foam composition (i.e., the polymer matrix), which may include one or more polymers, is present in an amount of at least 60 wt%, at least 65 wt%, at least 70 wt%, at least 75 wt%, at least 80 wt%, at least 85 wt%, or at least 90 wt%, based on the total weight of the foam composition (i.e., the final (dried) foam, which may include residual water). In certain embodiments, the polymer component of the foam composition, which may include one or more polymers, is present in an amount of up to 99.5 wt%, based on the total weight of the (final) foam composition. The remainder of the foam composition includes gas (e.g., air) dispersed therein, and may also include one or more blowing agents (e.g., expandable microspheres), residues of such blowing agents after the composition is foamed (e.g., expanding microspheres), fillers, and other optional additives, which are described in more detail below. In certain preferred embodiments, the remainder of the foam composition includes gas and expanding microspheres (i.e., the blowing agent residues resulting after the composition is foamed and the expandable microspheres are expanded), as discussed below.

[0042] The polymer component of the foam composition is formed using a solution of a polymer or a mixture of polymers in a solvent. The polymer may be soluble in the solvent, the polymer may be an emulsion, or the polymer may be a polymer dispersion. The solvent may be water or any organic solvent, including but not limited to isopropyl alcohol, ethanol, methanol, methyl ethyl ketone, ethyl acetate, hexane, heptane, methyl acetate, acetone, xylene, toluene, benzene, or a blend of solvents.

[0043] The polymer component of the foam composition is typically selected to be foamable and at least partially water soluble, and preferably may be formed using a water-based polymer or blend of polymers that provides one or more of the following properties to the foam padded material or packaging article: impact protection, cushioning, insulation, compression resistance, water resistance, regenerability, biodegradability, and / or composability.

[0044] To be foamable, such polymers are generally highly plasticized with water or solvents. This allows for efficient foaming, especially when the foaming is provided by the expansion of expandable microspheres upon heating. Water-based polymers are typically prepared by emulsion polymerization using a single grade or a mixture of emulsion polymers, which may be of synthetic or natural origin.

[0045] In certain embodiments, the polymer component is a polymer selected from the group including butanediol vinyl alcohol polymer or copolymer, starch, vinyl acetate / ethylene copolymer, polyvinyl acetate, polyvinyl alcohol, dextrin stabilized polyvinyl acetate, vinyl alcohol / vinyl acetate copolymer, vinyl alcohol / vinyl acetate / ethylene copolymer, stabilized polyvinyl acrylate copolymer, vinyl(methyl)acrylic, styrene (meth)acrylic, (meth)acrylic, styrene butyl rubber, natural rubber, styrene block copolymer, polyurethane, polyethylene, polyethylene oxide, polyethylene glycol, polyacrylic acid, polymethacrylic acid, polyvinylpyrrolidone, polyacrylamide, polypropylene glycol, polypropylene oxide, polylactic acid, polyglycolic acid, polycaprolactone, polybutylene succinate, polybutylene adipate terephthalate, cellulose, and mixtures or copolymers thereof.

[0046] One such commercially available polymer is a polyvinyl alcohol stabilized vinyl acetate ethylene (VAE) emulsion available under the trade name "DUR-0-SET" (Celanese, Florence, KY USA). In certain embodiments, the polymer can be neutral or can contain charged monomers (anionic, cationic, zwitterionic). One such commercially available polyvinyl alcohol polymer is a polyvinyl alcohol polymer available under the trade name "POVAL" and "MOWIFLEX" (Kuraray, Houston, TX, USA).

[0047] Polymers suitable for making foam compositions are typically obtained from suppliers in pellet or powder form and dissolved or dispersed in water or a solvent. Alternatively, they can be obtained as dispersions or emulsions. Typically, such dispersions or emulsions have a solids content of 10% to 70% by weight. Thus, the foam compositions (i.e., final foams) of the present disclosure are prepared from solvent-containing formulations referred to herein as "foamable" compositions.

[0048] In some embodiments, the solvent is water. In other embodiments, the solvent is an organic solvent and the polymer is soluble or dispersible in the organic solvent or can form an emulsion. Suitable polymers include, but are not limited to, polyesters, polyethers, polyolefins, polyamides, polyacrylates, polymethacrylates, polymethylmethacrylates, silicone or siloxane polymers, polyurethanes, polylactones, polylactams, polysulfides, polypeptides, polysaccharides, styrene polymers, blends of polymers, or copolymers.

[0049] Preferably, one or more polymers are water-soluble polymers. In the context of a polymer, water-soluble means that at least 90% by weight of the polymer dissolves in water at 130°F (54°C) in a procedure similar to the Water Solubility Test described in the Examples section. In certain embodiments, at least 95% by weight or at least 99% by weight of the water-soluble polymer dissolves in water at 130°F (54°C) in a procedure similar to the Water Solubility Test described in the Examples section.

[0050] In certain embodiments, the polymeric component comprises a copolymer, preferably a water-soluble polymer, comprising a divalent hydroxyethylene monomer unit (i.e., -CH2-CH(OH)-) and a divalent dihydroxybutylene monomer unit (referred to herein as a "hydroxy-ethylene-butylene copolymer"). In certain embodiments, the polymeric component may comprise one or more such hydroxy-ethylene-butylene copolymers (e.g., differing in monomer composition, molecular weight, melt flow index). In a preferred embodiment, the divalent dihydroxybutylene monomer unit is a 3,4-dihydroxybutane-1,2-diyl monomer unit (i.e., the structure [ka] (monomer units).

[0051] Optionally, but typically, the copolymer contains acetoxyethylene divalent monomer units (i.e., the structure [ka] The monomer unit further comprises

[0052] The copolymers can be obtained by copolymerization of vinyl acetate and 3,4-dihydroxy-1-butene followed by partial or complete saponification of the acetoxy groups to form hydroxyl groups. Alternatively, instead of 3,4-dihydroxy-1-butene, a carbonate, e.g. [ka] can also be used. After copolymerization, the carbonate can be hydrolyzed with simultaneous saponification of the acetate groups. In another embodiment, instead of 3,4-dihydroxy-1-butene, a compound of the formula: [ka] Acetals or ketals having the formula: wherein each R is independently hydrogen or alkyl (e.g., methyl or ethyl) can be used. After copolymerization, the carbonate can be hydrolyzed simultaneously with or separately from saponification of the acetate groups. The copolymers can be prepared by known methods or can be obtained, for example, from commercial sources.

[0053] Commercially available water-soluble copolymers include those available under the trade name "NICHIGO G-POLYMER" (Nippon Synthetic Chemical Industry, Osaka), a highly amorphous polyvinyl alcohol believed to have divalent monomer units of hydroxyethylene, 3,4-dihydroxybutane-1,2-diyl, and optionally acetoxyethylene. Nippon Synthetic Chemical Industry also refers to the chemical name butenediol vinyl alcohol (BVOH) as "NICHIGO G-POLYMER." Exemplary materials include "NICHIGO G-POLYMER" grades AZF8035W, OKS-1024, OKS-8041, OKS-8089, OKS-8118, OKS-6026, OKS-1011, OKS-8049, OKS-8074P, OKS-1028, OKS-1027, OKS-1109, OKS-1081, and OKS-1083. Exemplary "G-POLYMER" is available from Soarus LLC (Arlington Heights, IL, USA) under the trade designation "OKS-8074P." These hydroxy-ethylene-butylene copolymers have a degree of saponification of 80 to 97.9 mole percent and are believed to further comprise an alkylene oxide adduct of the polyhydric alcohol containing 5 to 9 moles of alkylene oxide per mole of polyhydric alcohol.

[0054] The hydroxy-ethylene-butylene copolymer is selected to provide foamability, at least partial water solubility, and preferably durability and / or heat sealability to the foam composition. Physical properties of the hydroxy-ethylene-butylene copolymer that may contribute to such performance characteristics include melt flow index, molecular weight, melting temperature, and decomposition temperature.

[0055] In certain embodiments, one or more of the hydroxy-ethylene-butylene copolymers in the polymeric component have a melt flow index (measured at 210° C. with a load of 2.16 kg) of at least 0.1 grams (g) per 10 minutes (min), or at least 0.5 g per 10 minutes. In certain embodiments, one or more of the hydroxy-ethylene-butylene copolymers in the polymeric component have a melt flow index (measured at 210° C. with a load of 2.16 kg) of at most 60 g / 10 min, at most 50 g / 10 min, at most 40 g / 10 min, at most 30 g / 10 min, at most 20 g / 10 min, or at most 10 g / 10 min.

[0056] In certain embodiments, one or more of the hydroxy-ethylene-butylene copolymers in the polymeric component have a melting temperature (as measured by differential scanning calorimetry (DSC)) of at least 90° C., at least 140° C., or at least 155° C. In certain embodiments, one or more of the hydroxy-ethylene-butylene copolymers in the polymeric component have a melting temperature (as measured by DSC) of at most 220° C., at most 200° C., or at most 195° C.

[0057] These hydroxy-ethylene-butylene copolymers may be used alone as the polymeric component of the foam or in combination with other (second) organic polymers, which may or may not be water-soluble.

[0058] In certain embodiments, the one or more hydroxy-ethylene-butylene copolymers are present in the polymeric component in an amount of at least 1 wt%, at least 10 wt%, at least 15 wt%, at least 25 wt%, at least 50 wt%, at least 60 wt%, or at least 70 wt%, based on the total weight of the polymeric components of the (final) foam composition. In certain embodiments, the one or more hydroxy-ethylene-butylene copolymers are present in the polymeric component in an amount of up to 100 wt%, up to 90 wt%, or up to 80 wt%, based on the total weight of the polymeric components of the (final) foam composition. These values ​​also characterize the polymeric components prior to foaming when the water of the foamable composition is not included.

[0059] In certain embodiments, the foamed composition is formed from a foamable water-containing composition comprising at least 1 wt%, at least 10 wt%, at least 15 wt%, at least 25 wt%, at least 50 wt%, at least 60 wt%, or at least 70 wt% of a hydroxy-ethylene-butylene copolymer based on the total weight of the (final) foamed composition. In certain embodiments, the foamed composition is formed from a foamable water-containing composition comprising up to 99.5 wt%, up to 95 wt%, up to 90 wt%, up to 80 wt%, up to 70 wt%, or up to 60 wt% of a hydroxy-ethylene-butylene copolymer based on the total weight of the (final) foamed composition.

[0060] In certain embodiments, the foamed composition is formed from a foamable water-containing composition comprising at least 1 wt%, at least 10 wt%, at least 15 wt%, at least 25 wt%, at least 50 wt%, at least 60 wt%, or at least 70 wt% of a hydroxy-ethylene-butylene copolymer based on the total weight of the (final) foamed composition. In certain embodiments, the foamed composition is formed from a foamable water-containing composition comprising up to 99.5 wt%, up to 95 wt%, up to 90 wt%, up to 80 wt%, up to 70 wt%, or up to 60 wt% of a hydroxy-ethylene-butylene copolymer based on the total weight of the (final) foamed composition.

[0061] In certain embodiments, the polymer component comprises a polymer or copolymer, preferably a water-soluble polymer or copolymer comprising polyvinyl alcohol units. Polyvinyl alcohol (PVOH) is a water-soluble polymer commercially available under the trade name "POVAL" from Kuraray America (Houston, TX USA) or "SELVOL" from Sekisui Specialty Chemicals America, LLC (Dallas, TX USA). Polyvinyl alcohol is available in various molecular weights and degrees of hydrolysis. Polyvinyl alcohol is synthesized by hydrolysis of polyvinyl acetate. The degree of hydrolysis refers to the amount of acetate groups converted to alcohol groups. Suitable degrees of hydrolysis range from 60% to 99%, or 70% to 95%, or 80% to 90%. The molecular weight of PVOH is proportional to its viscosity in water, e.g., a higher molecular weight PVOH has a higher solution viscosity at the same concentration. The viscosity measured in a 4% aqueous solution at 20° C. is in the range of 2 to 50 MPa*s, or 3 to 20 MPa*s, or 4 to 10 MPa*s.

[0062] In certain embodiments, the foamed composition is formed from a foamable water-containing composition that includes at least 1 wt%, at least 10 wt%, at least 15 wt%, at least 25 wt%, at least 50 wt%, at least 60 wt%, or at least 70 wt% of a PVOH polymer or copolymer based on the total weight of the (final) foamed composition. In certain embodiments, the foamed composition is formed from a foamable water-containing composition that includes up to 99.5 wt%, up to 95 wt%, up to 90 wt%, up to 80 wt%, up to 70 wt%, or up to 60 wt% of a PVOH polymer or copolymer based on the total weight of the (final) foamed composition.

[0063] In certain embodiments, the polymer component comprises a polymer or copolymer, preferably a water-soluble polymer or copolymer comprising acrylate units. Polyacrylate or polymethacrylate polymers and copolymers can be obtained by polymerization of acrylic acid esters, such as: [ka]

[0064] Polyacrylate (PA) polymers can be obtained as solids, liquid dispersions, or emulsions. Polyacrylate polymers are available from BASF (Houston TX) under the trade name JONCRYL. The variety and availability of acrylic ester monomers, polyacrylate polymers, and polyacrylate copolymers is extensive. Some well-known examples include polyacrylate, polymethyl acrylate, polymethyl methacrylate, polyethyl acrylate, polybutyl acrylate, polynorbornyl acrylate, polyacrylic acid, polyacrylamide, and polyacrylate polymers and copolymers, where R, for example, is: [ka] The range of ester groups is broad, with varying degrees of water solubility and / or degree of hydrolysis depending on the ester group represented by the formula: In certain embodiments, the foamed composition is formed from a foamable water-containing composition comprising at least 1 wt%, at least 10 wt%, at least 15 wt%, at least 25 wt%, at least 50 wt%, at least 60 wt%, or at least 70 wt% of a polyacrylate polymer or copolymer, based on the total weight of the (final) foamed composition. In certain embodiments, the foamed composition is formed from a foamable water-containing composition comprising up to 99.5 wt%, up to 95 wt%, up to 90 wt%, up to 80 wt%, up to 70 wt%, or up to 60 wt% of a polyacrylate polymer or copolymer, based on the total weight of the (final) foamed composition.

[0065] In certain embodiments, the polymer component comprises a polymer or copolymer, preferably a water-soluble polymer or copolymer, that comprises polyvinylpyrrolidone units. Polyvinylpyrrolidone (PVP) is a water-soluble polymer synthesized from N-vinylpyrrolidone monomers. [ka]

[0066] Polyvinylpyrrolidone is a hygroscopic amorphous polymer supplied as a white free-flowing powder or a clear aqueous solution. They are available in several molecular weight grades, characterized by their K value, and are used in a wide variety of applications. Polyvinylpyrrolidone can be plasticized with water and most commonly organic plasticizers. Applications exploit one or more properties inherent to the polymer, typically those due to the lactam ring. There is high polarity and, as a result, a tendency to form complexes with hydrogen donors such as phenols and carboxylic acids, as well as anionic dyes and inorganic salts. Components in a mixture are uniformly distributed with the use of polyvinylpyrrolidone, known as dispersibility. The considerable water solubility (hydrophilicity) of polyvinylpyrrolidone is its primary characteristic, a factor often combined with other properties that make it beneficial for a number of applications. Adhesion is the result of higher molecular weight polyvinylpyrrolidone formulated in an aqueous medium, with enough water allowed to evaporate to generate a solid product for the desired application. PVP materials are available from Ashland Chemicals in their product line under the trade name K-series.

[0067] In certain embodiments, the polymer component comprises a vinyl acetate ethylene (VAE) copolymer. The VAE copolymer is made from the copolymerization of ethylene and vinyl acetate monomers. The VAE copolymer typically has a vinyl acetate concentration range of 60-95 mol %, and the ethylene content can range from 5-40 mol %, and is supplied as an aqueous emulsion. VAE emulsion copolymers are sold under the trade name "DUR-O-SET" by Celanese Corporation (Irving TX). By varying the ethylene content of the VAE copolymer, the glass transition temperature Tg can be adjusted. The VAE glass transition temperature typically ranges from -15°C to 30°C. In certain embodiments, the foamed composition is formed from a foamable aqueous composition comprising at least 1 wt%, at least 10 wt%, at least 15 wt%, at least 25 wt%, at least 50 wt%, at least 60 wt%, or at least 70 wt% VAE copolymer. In certain embodiments, the foam composition is formed from a foamable water-containing composition comprising up to 99.5 wt%, up to 95 wt%, up to 90 wt%, up to 80 wt%, up to 70 wt%, or up to 60 wt% VAE copolymer, based on the total weight of the (final) foam composition.

[0068] In certain embodiments, the polymer or copolymer in the foamable composition has a Tg of at least -20°C, at least -15°C, at least 0°C, or at least 15°C. In certain embodiments, the polymer or copolymer has a Tg of at most 180°C, at most 75°C, at most 25°C, or at most 0°C. In certain embodiments, a blend of two or more polymers and / or copolymers is present, where one polymer has a Tg of at least -20°C and any additional polymer or copolymer has a Tg of at most 180°C. Ranges between these limits, for example, -20°C to 180°C, are within the scope of the present disclosure.

[0069] When used, the one or more second polymers are present in the polymer component in an amount of up to 99%, up to 90%, up to 80%, up to 75%, up to 60%, up to 50%, up to 40%, or up to 30% by weight, based on the total weight of the polymer component of the (final) foam composition. When used, the one or more second polymers are present in the polymer component in an amount of at least 10%, at least 20%, at least 30%, at least 40%, or at least 50% by weight, based on the total weight of the polymer component of the (final) foam composition.

[0070] In certain embodiments, the polymer component comprises a second polymer selected from the group of butanediol vinyl alcohol polymer or copolymer, starch, vinyl acetate / ethylene copolymer, polyvinyl acetate, polyvinyl alcohol, dextrin stabilized polyvinyl acetate, vinyl alcohol / vinyl acetate copolymer, vinyl alcohol / vinyl acetate / ethylene copolymer, stabilized polyvinyl acrylate copolymer, vinyl(methyl)acrylic, styrene (meth)acrylic, (meth)acrylic, styrene butyl rubber, natural rubber, styrene block copolymer, polyurethane, polyethylene, polyethylene oxide, polyethylene glycol, polyacrylic acid, polymethacrylic acid, polyvinylpyrrolidone, polyacrylamide, polypropylene glycol, polypropylene oxide, polylactic acid, polyglycolic acid, polycaprolactone, polybutylene succinate, polybutylene adipate terephthalate, cellulose, and mixtures or copolymers thereof. One such commercially available polymer is a polyvinyl alcohol stabilized vinyl acetate ethylene (VAE) emulsion available under the trade name "DUR-O-SET" (Celanese, Florence, KY USA). In certain embodiments, the polymer can be neutral or can contain charged monomers (anionic, cationic, zwitterionic). One such commercially available polyvinyl alcohol polymer is a polyvinyl alcohol polymer available under the trade name "POVAL" and "MOWIFLEX" (Kuraray, Houston, TX, USA). In certain embodiments, the polymeric material is regeneratively compatible. In other embodiments, the polymeric material is biodegradable. In yet other embodiments, the polymeric material is compostable.

[0071] In certain embodiments, the foamed composition is formed from a foamable water-containing composition that includes at least 20% by weight, at least 35% by weight, or at least 50% by weight of solids (i.e., anything other than water or solvent), based on the total weight of the foamable composition before foaming. In certain embodiments, the foamed composition is formed from a water-containing composition that includes up to 70% by weight, or up to 45% by weight, or up to 35% by weight of solids, based on the total weight of the foamable composition before foaming. The solids include the polymeric component, and any solid blowing agent (or solid residue remaining after foaming), fillers, and other optional solid additives. In certain embodiments, the foamed composition is formed from a foamable water-containing composition that includes a blowing agent, such as expandable microspheres. These are not required, as other mechanisms of foaming are possible, but as discussed below, if they are used, the expandable microspheres are present in an amount of up to 20% by weight, or up to 15% by weight, based on the total weight of the composition before foaming. In certain embodiments, if they are used, the expandable microspheres are present in an amount of at least 0.5% by weight, based on the total weight of the composition before foaming.

[0072] In certain embodiments, the expandable microspheres are thermally expandable polymeric microspheres, i.e., the expandable microspheres are capable of expanding in size in the presence of heat and / or radiant energy (including, for example, microwave, infrared, radio frequency, and / or ultrasonic energy).

[0073] Expandable microspheres have a particular temperature at which they begin to expand (initial expansion temperature or T0) and a second temperature at which they reach maximum expansion (maximum expansion temperature or T m ) Different grades of microspheres have different onset and maximum expansion temperatures. For example, one particularly useful microsphere has a T0 of 100° C. to 150° C. The temperature at which the microsphere reaches maximum expansion (T) is desirably between 100° C. and 200° C. The specific microspheres and their respective T0 and T mThe choice of is not critical, but the processing temperature may be changed depending on these temperatures. Before the composition is completely dry, these microspheres can move and expand within the composition. However, once the composition is completely dry, the microspheres are substantially fixed in place. The expanded composition typically has a total volume expansion of more than 2000%, preferably more than 2500%, from the wet or partially dried composition. There is a relationship between the evaporation temperature of the solvent and the initial activation temperature (T0) of the microspheres. In most cases, the solution is aqueous, and therefore the boiling point or evaporation temperature of water is 100°C. By using expandable microspheres with T0 less than 100°C, a lower percentage of foam dots with hollow cores are produced (as in Examples 108, 117, 118, and 119).

[0074] In certain embodiments, the expandable microspheres have a polymer shell and a hydrocarbon core (eg, a polyacrylonitrile or polyacrylonitrile copolymer shell).

[0075] Suitable microspheres include, for example, thermally expandable polymer microspheres, including those having a hydrocarbon core and a polyacrylonitrile shell (e.g., those sold under the trade name "DUALITE") and other similar microspheres (e.g., those sold under the trade name "EXPANCEL", e.g., "EXPANCEL 043 DU 80").

[0076] The expandable microspheres may have any unexpanded size, including from 5 microns to 30 microns in diameter. In the presence of heat, the expandable microspheres of the present invention may be capable of increasing in diameter by 3 to 10 times. When the microspheres in the composition expand, the composition becomes a foamed material. Alternatively, the expandable microspheres may be pre-expanded prior to combination with the polymeric component and allowed to fully expand without the need for further expansion.

[0077] The foam composition, and the water-containing foamable composition from which it is formed, may also include one or more additional optional additives. Examples of suitable optional additives include tackifiers (e.g., resin esters, terpenes, phenols, and mixtures of aliphatic, aromatic, or aliphatic synthetic hydrocarbon resins with aromatic synthetic hydrocarbon resins), plasticizers (other than physical foaming agents), nucleating agents (e.g., talc, silicone, or TiO2), colorants (e.g., pigments, dyes), reinforcing agents, solid fillers (e.g., pearl starch, physically modified starch, chemically modified starch, glass microspheres, clay, cork, sawdust, sand, inorganic particles (e.g., ceramic or metal), organic particles (e.g., carbon black particles, wood pulp, nanocrystalline cellulose, water-insoluble crosslinked polymer particles such as polystyrene-divinylbenzene), rheology modifiers, toughening agents, and the like. agents), thickening agents (e.g., water soluble cellulose ethers, fumed silica, thermoplastic starch, charged or uncharged synthetic polymers or oligomers which can be linear, branched, hyperbranched, dendritic, or star-shaped in structure), flame retardants, preservatives (e.g., biocides, 1,2-benzisothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, and 2-methyl-4-isothiazolin-3-one), antioxidants, defoamers, crosslinking agents (which increase the structural integrity of the composition after the microspheres are expanded), waxes (e.g., paraffin wax, beeswax, synthetic polyethylene wax), stabilizers (e.g., UV stabilizers), antioxidants, anti-yellowing agents, wetting agents, accelerators, antistatic agents, antiblocking agents, slip agents, and combinations thereof.

[0078] Optional release agents, sometimes referred to as low adhesion backside (LAB) coatings, can be added to the formulation to promote slip or reduce the foam's coefficient of friction. These release agents can include vinyl-silicone copolymers as disclosed in U.S. Pat. No. 5,032,460 (Kantner et al.). Additional LAB release agent formulations can include long alkyl chain acrylic copolymers as disclosed in U.S. Pat. No. 5,225,480. Preferably, the LAB used is water dispersible, providing an inherently renewable paper coating. Other release agents can include waxes, nanoparticles, microparticles, talc, and calcium carbonate.

[0079] The optional additives may be used in various combinations and amounts sufficient to obtain the desired properties for the foam produced. Typically, one or more such additives are present in an amount of at least 0.05% by weight, based on the total weight of the foamable water-containing composition (before foaming). In certain embodiments, the one or more optional additives are in an amount of up to 15%, up to 10%, or up to 5% by weight, based on the total weight of the foamable water-containing composition (before foaming).

[0080] The foamable compositions of the present disclosure desirably have a viscosity that allows for high speed printing / coating / spraying / spraying / overlaying or similar processes for deposition onto a substrate. Useful ranges of viscosity include 300 to 100,000 cPs at 25° C., desirably 1000 cPs to 70,000 cPs at 25° C., as measured using a rheometer at shear rates of 0.1 to 11 Hz per second according to the Brookfield Viscosity Test in the Examples section. In certain embodiments, the foam composition is coated from a solution having a viscosity of at least 500 cP, at least 1000 cP, at least 1,500 cP, or at least 15,000 cP. In certain embodiments, the foam composition is coated from a solution with a viscosity of up to 25,000 cP, up to 15,000 cP, up to 10,000 cP, up to 5,000 cP. In certain embodiments, the foam composition is coated from a solution at a viscosity range of 1,000 cP to 25,000 cP, or 1,000 cP to 15,000 cP, or 1,000 cP to 5000 cP.

[0081] A variety of methods of printing, coating, spraying, painting, overlaying, or otherwise applying the foamable water-containing composition to a substrate may be used to form the foamable composition of the present disclosure. In particular, rotogravure printing methods may be used, as described in the Examples section.

[0082] In patterned rotogravure printing, solution droplets ranging in diameter from at least 1 mm are placed with at least 1 mm spacing between dots. Rotogravure printing patterns can be tailored to deposit the solution in a variety of geometric shapes, such as circles, ellipses, rectangles, continuous or discontinuous lines, etc. Since discrete dots are believed to be necessary to generate foam bubbles with hollow interiors and porous exterior shells, a substrate coated over the entire substrate will not have the same foam structure as if discrete foam dots were coated and dried.

[0083] Following application of the foamable aqueous composition to a substrate by pattern coating as described herein, the coated substrate is exposed to conditions that cause foaming of the foamable composition. This preferably involves exposing the coated substrate to elevated temperatures for a time effective to form a foam and adhere the foam to the substrate. In certain embodiments, the drying temperature is equal to or greater than the melting temperature of the polymeric component of the foamable composition. For aqueous solutions, preferred drying temperatures can range from 130°C to 200°C, with drying residence times of 30 seconds to 60 seconds. If the temperature and / or time of this step is too low, a foam may form, but the foam may not adhere well to the substrate or form a sufficient microstructure to provide cushioning or other desired functionality.

[0084] During drying of the foam composition, the surface of the deposited liquid dot under certain conditions can cover the surface of the dot. As the solution continues to dry and the solvent evaporates below the covered surface, pressure is created by the evaporating solvent, pushing the skin surface up and away from the substrate, creating a bubble with a hollow core. The shell of the dot includes polymer resins, expandable microspheres, and various fillers that become a porous shell after drying is complete. The porous shell encapsulates the hollow core and attaches the foam to the substrate.

[0085] The porosity of the exterior shell is influenced by the weight percent of expandable microspheres in the foam composition. The porosity of the foam exterior shell can be up to 50% porous, 60% porous, 70% porous, 80% porous, or even 90% porous. The porosity of the foam shell is preferably at least 1% porous, at least 10% porous, or at least 50% porous. Ranges between these limits are also within the scope of the present disclosure. The thickness of the porous shell can be important to the overall mechanical stability of the porous shell hollow core foam dot. Foam dots with too thin a shell are detrimental to the durability of the foam. Foam dots typically have a porous shell that is at least 100 microns, at least 50 microns, or at least 25 microns thick.

[0086] The hollow core contained within the foam cell can affect the resulting foam properties. For a given droplet size, the larger the hollow core, the larger the overall foam dot in all dimensions (height, width, and length). The hollow core expands during drying while the shell wall thins. The size of the hollow core can be affected by variables such as the % solids of the foam solution, drying conditions, type and / or blend of solvents, and the aspect ratio of the deposited droplets.

[0087] In combination with a porous shell and hollow core foam structure, the size of the printed foam cells, the density of the foam pattern, the cell shape, the cell height, the cell diameter, and the shell thickness all play a role in determining the resulting material properties.

[0088] In certain embodiments, the hollow core has a diameter of at least 0.2 mm as measured by optical microscopy or x-ray tomography. 3 , at least 3 mm 3 , or at least 56 mm 3 In other embodiments, the hollow core has a volume of up to 56 mm as measured by optical microscopy or x-ray tomography. 3 , max. 10mm 3 , or up to 3 mm 3 The hollow core volume is 0.2 mm 3 ~250mm 3 , 5mm 3 ~100mm 3 , or 10mm 3 ~50mm 3 It can be.

[0089] In other embodiments, the total foam bubble volume is at least 0.2 mm as measured by optical microscopy or x-ray tomography. 3 , at least 10 mm 3 , at least 50 mm 3 , at least 70mm 3 , or at least 125 mm 3In other embodiments, the total foam cell volume is up to 400 mm 3 , up to 300mm 3 , or up to 200 mm 3 The range between these values, e.g. 0.2 mm 3 ~400mm 3 is within the scope of the present disclosure. The hollow core percentage as a function of total volume can be determined based on the hollow core volume and the total foam volume, and suitable percentage ranges using the above ranges for hollow core volume and total foam volume are within the scope of the present disclosure.

[0090] The foam shell provides some of the physical properties imparted to the foam, such as seam strength, coefficient of friction, cushioning, and abrasion resistance. For a given polymer system, properties such as seam strength and cushioning may improve as the shell thickness increases. Other physical properties, such as coefficient of friction, may be affected by the polymer resin selected, as well as the loading, type, and degree of expansion of the microspheres in the shell, which in turn may affect the shell thickness.

[0091] In certain embodiments, the thickness of the shell ranges from 0.04 mm to 0.94 mm, more preferably from 0.15 mm to 0.75 mm, more preferably from 0.2 mm to 0.55 mm, In certain embodiments, the porous shell has a thickness of at least 0.1 mm, at least 0.2 mm, or up to 1.0 mm.

[0092] In some embodiments, the porosity of the foam outer shell is at least 10% porous, at least 25% porous, at least 50% porous, at least 60% porous, at least 70% porous, at least 80% porous, or at least 90% porous, or at least 95% porous. Ranges between these values, such as 60% to 90% porous, are within the scope of the present disclosure. In some embodiments, the total porosity of the foam dot (hollow core + porous outer shell) is at least 50% porous, at least 60% porous, at least 70% porous, at least 80% porous, at least 95% porous, or up to 99% porous.

[0093] Shell porosity is affected by the microsphere loading of the dry composition. In certain embodiments, the microsphere weight percent of the total dry foam composition ranges from 1% to 12% by weight, more preferably from 1% to 6% by weight, and more preferably from 1% to 4% by weight.

[0094] Foam height is an important factor in controlling cushioning behavior. Foam height in combination with the foam's mechanical properties can affect the overall cushioning behavior. Generally, thicker foams provide a longer overall stopping distance for an object when dropped. Assuming the foam material has adequate compression properties for a range of weights, thicker materials can provide better protection.

[0095] However, this must be balanced against a number of other considerations in the intended use, such as cost and volume. Therefore, it is preferred not to have a foam material thicker than necessary to protect the item. In certain embodiments, the foam cells have a height in the range of 0.5 mm to 30.0 mm, in the range of 1.0 mm to 12 mm, in the range of 2.0 mm to 6 mm, and more preferably in the range of 1.0 mm to 3.0 mm.

[0096] The article in some embodiments may be renewable, compostable, and / or biodegradable. In many cases, the substrate on which the foam is coated is paper-based, which is naturally renewable, compostable, and biodegradable. Foam coating may reduce the compatibility of the packaging article with these processes. Therefore, in some applications, it may be important to balance the amount of foam deposited on the substrate to keep the final article renewable, compostable, and / or biodegradable.

[0097] The amount of foam that can be applied varies depending on the chemistry selected. In certain embodiments, the basis weight of the coating ranges from 5 to 90 gsm, more preferably 20 to 60 gsm, or 30 to 60 gsm, and most preferably 25 to 55 gsm. In some embodiments, the basis weight is at least 30 gsm or at least 55 gsm.

[0098] In certain embodiments, the basis weight of the dried foam coating is equal to the basis weight of the substrate, hi certain embodiments, the basis weight of the coating ranges from 1-90% of the basis weight of the substrate, from 2%-50% of the basis weight of the substrate, and more preferably from 5%-25% of the basis weight of the substrate.

[0099] The foam structure can have a hollow core and a porous outer shell, resulting in a material with a larger total volume after coating and drying. The size of the hollow core can vary widely depending on the solution solids, the pattern used for coating, and other parameters included within this application. In certain embodiments, the % of the total cell volume of the hollow core ranges from 5-99% of the total cell volume, or between 10-70% of the total cell volume, and more preferably between 10-50% of the total cell volume.

[0100] Coated Substrate The present disclosure provides coated substrates comprising a sheet material having a surface having disposed thereon a foam composition as described herein. Such coated substrates can be used in packaging materials to provide padding and to impart one or more of the following properties to the foam padded material or packaging article: impact protection, cushioning, thermal insulation, compression resistance, water resistance, regenerability, biodegradability, and / or compostability.

[0101] Examples of suitable substrates include woven materials, such as textile or woven materials, and nonwoven materials. In some embodiments, the woven or nonwoven materials use materials such as cotton, linen, and other natural fibers. In some embodiments, the woven or nonwoven materials use synthetic, organic, or non-organic materials, such as polyester, polylactic acid, polyethylene, polypropylene, carbon fiber, glass fiber, or wood fiber. In some embodiments, the substrate comprises cellulose fibers (e.g., paper). Other examples of suitable substrates include film sheets using natural or synthetic materials, such as polymer films (including, but not limited to, polyester, polyolefin, polylactic acid, vinyl, acrylic, and rubber), metal foils, or metallized polymer sheets.

[0102] In some embodiments, the film or paper substrate uses one or more surface modification treatment steps, such as corona treatment, plasma treatment, vapor deposition, chemical etching, or chemical or polymer coating. Suitable substrates can have a thickness ranging from 1 mm to 5 cm. In some embodiments, the substrate is corrugated (paper, cardboard, etc.). In certain embodiments, the substrate is paper having an elongation ranging from 0.1 to 10% as measured according to ASTM D882. In certain embodiments, the substrate is paper having a breaking load at break ranging from 1 to 50 N as measured according to ASTM D1306. In certain embodiments, the substrate is paper having a tear force of 1 to 300 grams as measured using the pendulum method (Elmendorf tear) according to ASTM D1922. These attributes of paper are believed to be important when using the foam coated substrate as a mailing container or wrap to protect items during shipping.

[0103] In certain embodiments, the coated substrate is optionally a renewable and / or compostable and / or biodegradable foam padded material suitable for use in making packaging articles. More specifically, the foam padded material comprises a sheet material having first and second major surfaces, the sheet material being optionally a renewable, compostable, or biodegradable material, and a foam composition disposed on the first major surface of the sheet material, the foam composition comprising a polymer component that forms a plurality of structures (dots) on the sheet material having a hollow core and a porous outer shell.

[0104] The foamed composition may form a continuous or discontinuous coating on the surface of a substrate (e.g., a sheet material), or a combination of the two. In certain embodiments, the foamed composition is arranged in a discontinuous pattern comprising an array of discrete elements. Such discrete elements can be in the form of a wide variety of geometric shapes, such as, for example, squares, rectangles, triangles, spirals, lines, circles, and / or combinations of the mentioned geometric shapes.

[0105] In other embodiments, the final foam composition 16 can have a continuous or substantially continuous overall coating 18 on the first major surface 12 of the sheet material 10, and then a discontinuous pattern 20 comprising an array of discrete elements disposed on the continuous coating, as shown in Figures 12A and 12B. Utilizing both coating layers can improve the heat sealability of the foam composition because it has a continuous coating layer between the discrete foam dots or elements, while also having significant cushioning capabilities due to the discontinuous pattern coating layer. As shown in Figure 11, a rotogravure roll with the appropriate cell pattern can apply both coating layers in a single printing pass. Alternatively, the different coating layers can be applied by two coating stations with different rotogravure rolls.

[0106] In a discontinuous pattern, there are spaces between elements in an array of elements. The pattern is selected to allow for proper expansion of the expandable composition upon deposition onto the substrate surface. Any selected pattern may include one or more variations in spacing for expansion. For example, discrete regions of the composition may be used that are not connected or discontinuous to other discrete regions of the composition, or discrete regions of the expandable composition may be used in combination with connecting bridges between the discrete regions such that they are connected but still provide expansion space. The discrete regions may be of any shape or configuration that serves the purpose of providing protective padding upon expansion. Such patterns may be regular or irregular (i.e., including a random array of elements). Non-limiting examples of such patterns are shown in Figures 1A-1G. The patterns may be configured in a variety of ways to fit the final product and provide the desired padding. For example, the pattern may be a series of linear or non-linear spaced elements of the composition. These elements may be connected in one or more locations, may be arranged in parallel or non-parallel configurations, and may form, for example, recognizable text, images, or logos.

[0107] Each element of the array of discrete elements of the foam composition has a length and a width, typically with at least one dimension ranging from 0.05 inches to 2.0 inches (1.27 to 50.8 mm) and at least one dimension ranging from 0.1 inches to 2.5 inches (2.5 to 63.5 mm). In some embodiments, the foam composition may have a diameter of 0.5 mm to 10 mm, or 3 mm to 5 mm.

[0108] In some embodiments, the shell thickness can be between 0.02 mm and 2 mm, or between 0.2 mm and 1 mm, or between 0.2 mm and 0.5 mm.

[0109] The substrate surface area may be 100% covered by the discrete elements of the foam composition (i.e., foam), but typically is less than 100% covered. In certain embodiments, the foam composition covers at least 5%, at least 10%, at least 15%, at least 20%, at least 30%, at least 40%, or at least 50% of the substrate (e.g., sheet material) surface area. In certain embodiments, the foam composition covers 100%, or less than 95%, less than 90%, less than 85%, less than 80%, less than 70%, or less than 60% of the substrate (e.g., sheet material) surface area. Ranges between these limits are within the scope of the invention. Coverage may be higher in certain regions than in other areas. For example, coverage may be higher in regions on the substrate that form a seal with another substrate (e.g., at the edges of the sheet material that form the walls of an envelope). Alternatively, coverage may be lower or completely absent in regions on the substrate (e.g., on portions of the sheet material that form the flaps of an envelope).

[0110] In certain embodiments, the foam composition is disposed on the surface of the substrate (e.g., sheet material) in an amount (i.e., coating weight) of at least 5 grams per square meter (gsm), at least 10 gsm, at least 15 gsm, or at least 20 gsm, at least 30 gsm, at least 40 gsm, or at least 50 gsm. In certain embodiments, the foam composition is disposed on the surface of the substrate (e.g., sheet material) in an amount of up to 120 gsm, up to 110 gsm, up to 100 gsm, up to 90 gsm, up to 80 gsm, up to 70 gsm, up to 60 gsm, up to 50 gsm, or up to 40 gsm. Ranges between these limits, e.g., 10 gsm to 120 gsm, are within the scope of the present disclosure. This can be determined using the foam weight test described in the Examples section. In certain embodiments, the foam composition is disposed on the surface in a coating weight of 20 gsm to 60 gsm, 25 gsm to 55 gsm, or 25 to 45 gsm.

[0111] In other embodiments where both a continuous foam composition coating layer and a discrete element discontinuous foam composition coating layer are present, the coating weight range of the continuous foam coating can be 0-50 gsm, 5-30 gsm, or 5-20 gsm. The weight range of the discontinuous discrete foam elements can be 5-100 gsm, 10-80 gsm, or 15-70 gsm. The total coating weight on the substrate is the sum of the individual weight ranges.

[0112] In certain embodiments, the foamed composition (i.e., each element of the array of discrete elements of the foamed composition) disposed on a surface of a substrate (e.g., a sheet material) has a height of at least 0.25 mm, at least 0.5 mm, at least 1.0 mm, at least 2 mm, and often up to 10 mm, or even up to 50 mm.

[0113] In certain embodiments, the foam composition (i.e., each element of the array of discrete elements of the foam composition) is disposed on both opposing surfaces of a substrate (e.g., a sheet material). The patterns on the opposing surfaces may include the same pattern used on both surfaces, different patterns on the opposing surfaces, or one surface may be a discontinuous coating and the opposing surface may be a discontinuous and / or continuous coating. The foam composition may be exposed or may be covered or encapsulated (at least partially) by one or more sheet materials (e.g., paper or other cover sheets), such that the padding material forms a "sandwich" with the foam composition sandwiched between two sheet materials, which may be the same or different. Such foam padded materials may include, for example, paper / foam / paper or paper / foam / foam / paper structures, and may be used to create multi-layer padded mailing articles. Another sheet material, such as a nonwoven or film, may be substituted for the paper.

[0114] The renewable and / or compostable padded material can be provided in any size or shape, typically it is provided in roll form that can be easily cut into discrete lengths to form into packaging articles, such as envelopes or shipping wraps that are placed around transported articles to protect the transported articles.

[0115] Sheet material In some embodiments, the sheet material of the foam padded material and the walls of the packaging article comprise a biodegradable material. In some embodiments, the biodegradable material is paper. In other embodiments, the sheet material can be a biodegradable polymer, such as polyvinyl alcohol, polybutylene succinate, polysaccharides, polylactic acid, polyglycolic acid, or blends or copolymers. In certain embodiments, the sheet material of the foam padded material and the walls of the packaging article comprise a renewable material. In certain embodiments, the reusable material is a repulpable material, such as paper. In some embodiments, the sheet material of the foam padded material and the walls of the packaging article contain only repulpable paper and are therefore described as consisting of repulpable paper. The sheet material of the foam padded material and the walls of the packaging article can be one material or more than one material, and the materials constituting the first and second walls can be the same or different.

[0116] As used in this context, "paper" refers to a product or fabric in sheet form (which can be foldable and of various thicknesses), woven or nonwoven, made from cellulose (especially cellulose fibers (either natural or man-made)) or which may otherwise be derived from the pulp of plant sources such as wood, corn, grass, rice, etc. Paper includes products made from both traditional and non-traditional papermaking processes, as well as materials of the above types in which other types of fibers, such as reinforcing fibers, are embedded within the sheet. Paper may have a coating on the sheet or on the fibers themselves.

[0117] Any form of paper can be used, but it is preferred that the paper is repulpable (i.e., can be turned into pulp). Paper (or cellulose fibers) are inherently pulpable, but once papers are processed, their recyclability depends on the amount of fiber separated during the repulping process; for example, in the United States, there is a voluntary standard that specifies a minimum fiber recovery rate of 85%. This standard was developed by a joint committee of the Fibre Box Association and the American Forest & Paper Association (AF&PA).

[0118] In certain embodiments, the sheet material is a woven or nonwoven web, such as spunbond or meltblown. In some embodiments, the woven or nonwoven material is made of natural materials, such as cotton, linen, and other natural fibers. In some embodiments, the woven or nonwoven material is made of synthetic, organic, or non-organic materials, such as polyester, polylactic acid, polyethylene, polypropylene, carbon fiber, glass fiber, or wood fiber. In some embodiments, the substrate is made of cellulosic fibers (e.g., paper).

[0119] In certain embodiments, the sheet material is a film. Examples of suitable substrates include film sheets made of natural or synthetic materials, such as polymeric films (including but not limited to polyester, polyolefin, polylactic acid, vinyl, acrylic, and rubber), metal foils, or metallized polymer sheets. In some embodiments, the film substrate or paper substrate is configured with one or more surface modification treatment steps, such as corona treatment, plasma treatment, vapor deposition, chemical etching, or chemical or polymer coating.

[0120] Exemplary paper sheet materials include kraft liner paper, fiberboard, chipboard, corrugated cardboard, paper medium, corrugated medium, solid bleached board (SBB), solid bleached sulphite board (SBS), solid unbleached board (SLB), white lined chipboard (WLC), kraft paper, kraft board, coated paper, internally sized paper, binder board, or mixtures thereof. Examples of non-traditional products that are "paper" within the context of this disclosure include the material available under the trade name "TRINGA" from PAPTIC (Espoo, Finland) and the sheet form of the material available under the trade name "SULAPAC". Kraft paper is particularly useful for this purpose, although other papers may be used.

[0121] Exemplary sheet materials that can be used have a basis weight sufficient to enable them to withstand weather conditions such as heat, cold, rain, or snow, and other conditions that may be encountered during the packaging and shipping process, as well as to withstand handling that may occur during packaging and shipping, such as dropping, jostling, hitting other materials, etc. Any basis weight suitable for the intended use may be used, and various basis weights may be suitable depending on the needs of the user. Most commonly, basis weight (grams per square meter (g / m2)) is used to measure the surface area of ​​the sheet. 2 or gsm) is at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70 gsm. Most commonly, the basis weight (g / m 2The basis weight (in gsm) is up to 200, up to 150, up to 140, up to 130, up to 120, up to 110, up to 100, up to 75, up to 70, up to 65, up to 60, up to 55, up to 50, up to 45, up to 40, up to 35, up to 30, or up to 25 gsm. Most commonly, the basis weight (in g / m 2 ) is a unit of thickness ranging from 30 to 200 gsm.

[0122] In certain cases, a single sheet of material is folded to create both the first and second walls from the same sheet of material, thereby providing the first and second walls with the same components and made from the same material. This may be particularly advantageous to facilitate assembly or manufacturing of packaging articles such as envelopes, mailers, or tubes. In such embodiments, it may be preferred to leave the fold and / or seal lines uncoated with the foamable composition. FIG. 21 shows a sheet material 10 having a foam composition 16 disposed on a first major surface in two major regions, and also having an uncoated fold or seam region 31 extending the length of the sheet material such that when the sheet material is folded in half, the foam composition 16 does not interfere with the folding operation in the packaging equipment and a crisp crease is formed.

[0123] In some embodiments, one end or edge of the sheet can overlap the opposing end or edge of the sheet to form a tube. The tube can be sealed by attaching the overlapping portions. The resulting tube can be open at both ends. It is possible to seal both of the last two openings after an object is placed in the package, or it is possible to seal one opening, then place an object in the package, and then seal the remaining opening. This can be accomplished by methods described herein or known in the art, such as by using a bag sealing machine, impulse sealer, heat sealer, etc.

[0124] It is not necessary that the first wall and the second wall are made of the same material sheet. It is also possible to attach two sheets of different materials to make an article with a first wall and a second wall having different materials, such as paper and a polymer film. This may be advantageous for some intended uses, so the embodiment assembled in this way is also important. It is also possible to attach two sheets of the same material, rather than folding one sheet, which is less common, but may be an important mode of implementing the present disclosure for some intended uses of packaging articles.

[0125] The first wall, the second wall, or both, may be comprised of a single layer or sheet of material, or multiple sheets.

[0126] When multiple sheets (i.e. layers) are used for the first wall, the second wall, or both, they can be the same or different layers or sheets. Two, three, four, or even more layers or sheets can be used. In configurations where there are two layers or sheets, one sheet is an inner layer or sheet disposed on the interior of the applicable wall, and the other layer or sheet is an outer layer of a sheet disposed on the exterior of the applicable wall. In configurations where there are three layers or sheets, there is an additional intermediate layer or sheet between the inner and outer layers or sheets. The foamable composition can be disposed between any of the sheets forming the walls, and / or on the inner surface and / or on the outer surface of the sheets.

[0127] One or more of the layers or sheets may be flat layers or sheets. It is also possible that one or more of the layers or sheets may be embossed (before depositing the foam thereon). An embossed layer or sheet may provide some additional cushioning to the contents of the packaged article and may therefore be advantageous in certain applications. Any embossing pattern may be used, but most often a regular or repeating pattern is used. Examples of repeating patterns are diamonds, squares, circles, triangles, hexagons, as well as mixed patterns with different shapes. When multiple layers or sheets are used, any or all of the layers or sheets may be embossed. Most commonly, when two layers or sheets are used, the inner layer or sheet is embossed and the outer layer or sheet is not embossed. When three layers or sheets are used, typically either the middle layer or the inner layer or sheet is embossed and the other layer or sheet is not embossed. However, other configurations are possible. For example, in a three-layer structure, it may be useful to emboss both the inner and middle layers or sheets to provide additional cushioning beyond that provided by only one embossed layer or sheet.

[0128] Any of the layers or sheets may include a coating that is considered to be part of the layer or sheet. Suitable coatings, which may be selected depending on the requirements of the article or the end use, may include at least one of polyester, poly(butylene succinate), poly(butylene succinate adipate), silicone, fluorinated polymer, acrylic, acrylate, poly(ethylene succinate), poly(tetramethylene adipate-co-terephthalate), castor wax, or thermoplastic starch, specifically, poly(butylene succinate), poly(butylene succinate adipate), poly(ethylene succinate), castor wax, or poly(tetramethylene adipate-co-terephthalate), more specifically, poly(butylene succinate), castor wax, or both poly(butylene succinate) and castor wax, most specifically, poly(butylene succinate).

[0129] packaging goods Packaging articles, particularly those designed for shipping, such as mailers, envelopes, bags, pouches, and boxes, are described herein. The packaging articles can also be in the form of cushioning materials or wraps, in which an item is wrapped with one or more layers of sheet material to provide protective cushioning around an item that is shipped within another packaging article, such as a box. Alternatively, the material forming the box may be coated to have a cushioning layer on either the inside or outside of the box, or both, and the foamable composition can, in some embodiments, serve to heat seal the flaps of the closed box.

[0130] Packaging articles can take a variety of forms. For example, the article can be a pouch, a bag, a box, a mailing container, or an envelope. Still other forms are possible. Regardless of its form, the article can be completely closed, for example, with an object inside the article, or it can have an opening. The article typically has two walls, a first wall and a second wall, each having an inner surface facing the interior of the article and an outer surface facing the exterior of the article. Thus, the inner surface of the first wall ("first inner surface") faces the inner surface of the second wall ("second inner surface").

[0131] As discussed above, the inner surface of the wall, which may be the coated surface, is the surface of the sheet material that includes the foam composition disposed thereon. The foam composition may be exposed to the interior of the packaging article, in which case no additional sheets or layers are disposed on top of the foam composition. Alternatively, one or more additional layers of sheet material may be disposed on top of the foam composition in the form of one or more cover sheets. In those cases, the packaging article has a structure with the foam composition sandwiched between two sheets or layers of material. The cover sheet may comprise the same or different material as the material that constitutes the wall. Such a wall may comprise one layer of foam-coated sheet material plus a cover sheet, or two layers of foam-coated sheet material, thereby forming, for example, a paper / foam / paper or paper / foam / foam / paper structure. Examples of such multi-layer padded mailing articles are shown, for example, in Figures 10A-C. Such cover sheets may reduce friction experienced by items inserted into the padded mailing article.

[0132] The two walls are typically manufactured from a sheet of material, which may be a single layer of material or multiple layers of material. Each of the walls may be manufactured from a different sheet, in which case the two walls may be manufactured from the same or different materials. More commonly, the first and second walls are manufactured from the same sheet of material, which is folded to produce two separate walls. In these cases, the first and second walls may be made of the same material.

[0133] The first and second walls are attached along at least one edge of the packaging article. Depending on the configuration and shape of the article, they can be attached along two, three, four, or even more edges. The first and second walls can be directly attached so as to be sealed together, or can be indirectly attached by intermediate structures such as gussets, welding, or the like. The packaging article can also include an opening where the first and second walls are not attached.

[0134] The packaging article can include an opening where the first and second walls are not attached, however, an opening is not required as it is also possible to form the packaging article around an object located therein, thereby eliminating the need to manufacture an article with an opening and subsequently close the opening.

[0135] The packaging article includes a foam composition disposed on at least a portion of each of the first and second inner surfaces. The foam composition may form a continuous or discontinuous coating on each of the first and second surfaces. In certain embodiments, the foam composition is disposed in a discontinuous pattern comprising an array of discrete elements. Such discrete elements can be in the form of a wide variety of geometric shapes, for example, squares, rectangles, triangles, spirals, lines, circles, etc. The spacing, size, density, etc. of the foam composition disposed on the inner surfaces of the packaging article can be the same as those described herein for the foam padded material.

[0136] When used, the one or more cover sheets placed on the foam structure can be made of any suitable sheet material or layer. Most commonly, the cover sheet is made of a paper or nonwoven sheet or layer. When paper is used, the paper can be any type of paper depending on the intended use, such as kraft paper, white paper, crepe paper, etc. When nonwoven is used, it can be any sheet nonwoven, such as one made of one or more polymers or copolymers of lactic acid, lactide, glycolic acid, glycolide, caprolactone, etc. The one or more cover sheets can be coated on one or both sides, for example, with a heat-sealable coating that can include, for example, at least one of poly(butylene succinate), poly(butylene succinate adipate), silicone, fluorinated polymer, acrylic, acrylate, poly(ethylene succinate), poly(tetramethylene adipate-co-terephthalate), castor wax, or thermoplastic starch, specifically, poly(butylene succinate), poly(butylene succinate adipate), poly(ethylene succinate), castor wax, or poly(tetramethylene adipate-co-terephthalate), more specifically, poly(butylene succinate), castor wax, or both poly(butylene succinate) and castor wax, most specifically poly(butylene succinate).

[0137] When used, one or more cover sheets can be secured in place by being secured to all or a portion of the foam composition, or, if not all of the interior surface of the wall is covered by the foam composition, by being secured to one or more portions of the interior surface of the wall that do not contact the foam composition. This can be accomplished by lamination, heat sealing, adhesives, etc., or, if the cover sheet is secured to the foam, by using the foam composition itself as the adhesive, which can be accomplished by contacting the cover sheet with the foam composition while it is not fully cured.

[0138] One or more cover sheets may be used. When cover sheets are used, most commonly the inner surfaces of both walls are covered by the cover sheet. However, this is not required. It should be understood that the use of a cover sheet is optional.

[0139] The packaging articles of the present disclosure also include a seal joint at one or more edges of the first and second walls, In most cases, the seal joint includes or is formed from a foam composition that attaches the first wall to the second wall.

[0140] In making the packaging article, the sheets can be joined together in any suitable manner to form a seal joint at one or more edges of the sheet material (e.g., forming the first and second walls of the packaging article). Preferably, the seal joint can be formed using a foaming composition to attach the first wall to the second wall. Preferably, the foaming composition described herein can be a heat-sealable composition, in which case the sheets can be joined together by a heat sealing process, induction welding, ultrasonic welding, or impulse sealing. A patterned calendar roll or pressure roll can also be used to bond adjacent layers. Alternatively, the foaming composition can be a watertight composition, thereby forming a seal joint upon application of water.

[0141] FIG. 2 shows an exemplary packaging article structure in which the two edges of the first and second walls are attached. In FIG. 2, the article 100 is configured as a bag. The first and second edges 110, 112 are directly attached and join the first wall 130 with the second wall 140. Only the outer surface 131 of the first wall 130 and the inner surface 142 of the second wall 140 are visible in this view. The opening 150 exists when the first and second walls 130, 140 are not attached. In this case, the bottom 120 is defined by the folds of the sheet material that makes up the article 100.

[0142] 3 shows an alternative structure in which only one edge of the first and second walls is attached, where the exemplary article 200 is also configured as a bag. The single edge 211 attaches to most of the first and second walls 230, 240, leaving them unattached at the opening 250.

[0143] FIG. 4 shows the structure of an exemplary packaging article 300 in which edges 311, 312 are in the form of gussets that attach to first and second walls 330, 340 while leaving an opening 350 unattached.

[0144] Figures 5 and 6 show another exemplary structure of a packaging article 400, which contains a flap 460 and is foldable between an open position, shown in Figure 5, and a closed position, shown in Figure 6. In the open position, the opening 450 is uncovered, while in the closed position, the opening 450 is covered by the flap 460.

[0145] Adhesive part In some embodiments, one or more adhesive portions may be provided. The adhesive portion is not considered to be part of the wall. Typically, when used, the adhesive portion is near the opening of the packaging article and can be used to close the article. When a flap is used, the one or more adhesive portions are often on the flap or on a portion of the outer surface that can be reached by the flap when it is folded into a closed position, thereby allowing the flap to be adhered in the closed position. Often, two adhesive portions are provided.

[0146] The adhesive portion or portions are typically in the form of a strip extending generally parallel to the opening of the packaging article, although this is not required. It is also possible for the adhesive portion or portions to be coated over one or more larger sections or portions of the article, such as, for example, a section or portion of one or more walls or flaps (if flaps are used).

[0147] The adhesive part or parts can be any suitable adhesive depending on the desired application, specifically, renewable, compostable, or recyclable, and most commonly recyclable. In this context, the term "recyclable" refers to materials or compounds that are not themselves renewable, but are easily separated from renewable materials during the recycling process, more specifically, during repulping. Thus, packaging articles can have components such as adhesives that are not themselves renewable, and still be renewable if the non-recyclable components are recyclable.

[0148] In certain cases, one or more adhesive parts are composed of renewable and / or compostable adhesives. One or more adhesive parts can be water-activated adhesives, heat-sealable adhesives, hot melt adhesives, or pressure-sensitive adhesives. Most specifically, pressure-sensitive adhesives are used. Examples of suitable adhesives include copolymers of 2-octyl acrylate and acrylic acid; copolymers of sugar-modified acrylates; blends of poly(lactic acid), polycaprolactone, and resins; blends of poly(hydroxyalkanoates) and resins; protein adhesives; natural rubber adhesives; synthetic rubber adhesives; and polyamides containing dimer acids.

[0149] When a heat sealable adhesive is used, it can be any heat sealable adhesive or hot melt adhesive. Most commonly, the heat sealable adhesive is one that can be sealed with medium or low heat by using an impulse sealer or a heat sealer, such as a handheld heat sealer. Many handheld heat sealers are commercially available for both home and commercial use, such as the Mini Bag Sealer (available from EEX Co., Ltd.) and the iTouchless Handheld Heat Bag Sealer (available from Amazon, USA). Examples of heat sealable adhesives that can be used include poly(butylene succinate), poly(butylene succinate adipate), silicone, fluorinated polymer, acrylic, acrylate, poly(ethylene succinate), poly(tetramethylene adipate-co-terephthalate), castor wax, or thermoplastic starch, specifically at least one of poly(butylene succinate), poly(butylene succinate adipate), poly(ethylene succinate), castor wax, or poly(tetramethylene adipate-co-terephthalate), more specifically poly(butylene succinate), castor wax, or both poly(butylene succinate) and castor wax. Most specifically, poly(butylene succinate) (sometimes called PBS) is used.

[0150] One or more release liners can be placed on any or all of the one or more adhesive portions. The release liners are advantageously compostable and / or recyclable, but this is not essential, since the release liners can be disposed of separately from the packaging article after use and do not need to be placed together with the packaging article in a composting and / or recycling environment. Thus, when the packaging article described herein has one or more release liners, the packaging article can be compostable and / or recyclable even if any or all of the release liners are not compostable and / or recyclable.

[0151] 7A shows an exemplary packaging article 500 having an adhesive portion 501. In this example, the packaging article 500 is formed as a bag, and the adhesive portion 501 is placed near the top of the opening 550 to close the opening 550 if necessary.

[0152] 7B shows an exemplary packaging article 600 having two adhesive portions 601 and 602. In this example, the packaging article 600 is formed as a pouch, and the adhesive portions 601 and 602 are disposed on a flap 660 to close an opening 650.

[0153] 8A and 8B are schematic diagrams of exemplary packaging articles, specifically, envelopes having uncoated flaps (i.e., a portion of the wall material forming the flap of the envelope that does not have a foam composition disposed thereon) having an adhesive strip disposed thereon to seal the flap when in a closed position.

[0154] When an article has one or more cover sheets, one or more adhesive portions can be present on the cover sheets. For example, when a heat-sealable coating such as poly(butylene succinate) is used as a coating on some or all of the cover sheets, the heat-sealable coating can function as an adhesive portion.

[0155] Easy-opening mechanism The features or characteristics may be present to facilitate easy opening of the packaged article after it has been sealed. Examples include perforations, scoring, zip tops, or embedded drawstrings or wires. If an opening or flap is present, one or more of these features may be present near the opening or flap to facilitate opening of the packaged article near the opening or flap, or may be present on different parts of the packaged article. These features, if used, are not required to have a specific configuration, most commonly in a straight line parallel to at least one edge of the packaged article, and other shapes or layouts may be used depending on the intended use of the packaged article.

[0156] Method of production and assembly Assembly of the packaging articles described herein can be accomplished by any suitable method.

[0157] One method of assembling the packaging article involves folding one or more layers or sheets, which are joined together when multiple layers or sheets are used to form a first wall and a second wall. When the packaging article is a bag, they can be folded in half. When the packaging article is a pouch or envelope, they can be folded so that there is a flap on the first wall that overhangs the edge of the second wall. The edges can then be attached by heat sealing, ultrasonic welding, impulse sealing, or the like to form the packaging article. The procedure is similar when the first and second walls are made of different materials, as long as one wall has a foam composition disposed therein, in which case all edges, in addition to the opening, can be sealed to form the final article.

[0158] An assembly can be formed by placing an object within any of the packaging articles described herein. The packaging article can then be closed, for example, by folding the flaps to a closed position and attaching the flaps to an exterior surface with at least one of the one or more adhesive portions.

[0159] The assembly and the packaging article can be formed together. For example, an object can be placed on the layer or sheet on which the article or assembly is formed. The article or assembly can then be folded around the object, and the edges can be completely sealed around the object. An article or assembly can be obtained in which the object is inside the packaging article or assembly, and the edges are sealed so that the object cannot fall out unless one or more seals are broken at the edge, or one or more of the layers or sheets are punctured, cut, torn, etc., to create an opening.

[0160] Reseal When one or more adhesive portions are used on the flaps, it is possible to reseal an opened packaged article. For example, an assembly can be formed as discussed above, and then the packaged article can be opened, for example, by tearing the flap of the packaged article at the perforated seal adhesive portion or by tearing the seal of the cover sheet. At this point, the adhesive portion can be utilized to reseal the packaged article. For example, this procedure can be followed when an item shipped in the packaged article is to be returned to the sender in the same packaged article. EXAMPLES

[0161] The following illustrative examples may aid in understanding the present disclosure. However, the present disclosure is not necessarily limited to these examples. There may be disclosed embodiments and concepts that are not specifically illustrated. Unless otherwise noted, all parts, percentages, ratios, etc. in the examples and the rest of the specification are by weight, and all materials used in the examples were obtained or were available from general suppliers, such as, for example, Georgia-Pacific, Atlanta, GA, US. [Table 1]

[0162] Test Method Brookfield Viscosity: The viscosities of the aqueous polymer dispersions were measured using a Brookfield DV-E Viscometer operating at 3, 10, or 30 revolutions per minute (rpm) using spindle #3. The actual spindle and rpm used are reported in Tables 2, 3, and 4.

[0163] Foam Weight: The foam weight was measured using TAPPI T 410 OM-19 "Basis Weight (Weight per Unit Area) of Paper and Paperboard." A 10 centimeter (10 cm) by 10 cm (4 in. by 4 in.) square was cut from each foam sample, weighed, and the total basis weight in gsm (grams per square meter) was calculated. To determine the coating weight of the foam alone, the basis weight of the substrate was subtracted from the total basis weight.

[0164] Foam Dots Characterization: The foam dots were characterized by optical microscopy. Shell thickness, dot diameter, dot height, foam dot volume, as well as hollow core volume and % hollow core volume were measured and calculated based on the following formula: Hollow core % volume ranged from 30-95% of the calculated volume. Total porosity of the samples was measured by X-ray tomography. Examples of optical micrographs from Example 101 are shown in FIG. 18.

[0165] The estimated bubble volume was calculated using the formula for the volume of a cylinder:

number

number

[0166] X-ray microtomography analysis: A strip of material was cut from each prepared sheet so that at least one foam structure (bubble) was fully intact and attached to a plastic support using double-sided tape to fix the sample during scanning. Each sample was scanned using a SkyScan 1172 Micro-CT scanner (Bruker CT, Kontich, Belgium) at a resolution of 3.99 μm (voltage: 40 kV, current: 250 μA). The sample was placed vertically (on its end) in a plastic tube and rotated 180° during scanning along the axis of rotation of the sample. The resulting raw 2D projection scan image was subjected to a reconstruction process using SkyScan software to generate individual 2D grayscale slices along the axis of rotation spaced apart at a scanning resolution of 3.99 μm. An example of the resulting scan for the sample of Example 117 is shown in FIG. 19.

[0167] For each reconstructed data set, a VOI (Volume of Interest) was created using SkyScan software (CTAnalyzer) to encompass the complete foam structure (bubbles) volume and exclude any air space around the foam structure (bubbles) and the exterior of the sample backing material. This VOI was subjected to 3D analysis (built-in module) in CTAnalyzer to determine the total foam structure (dot) volume (total volume of the VOI) and the total polymer matrix (solid material) volume as the object volume.

number

number

[0168] To determine the shell void volume of each sample structure (bubble), the reconstructed image stacks were loaded into Avizo software (Thermo Fisher Scientific, Waltham, MA) and binarized. The Compute Ambient Occlusion module was applied to the binarized dataset. The resulting dataset was a grayscale image stack of the structure's (bubble) shell void space, excluding the hollow core. The occlusion dataset was binarized a second time and the Label Analysis module was applied to the binarized occlusion dataset to measure the structure's (bubble) shell void volume. The sum of these volumes gave the total shell void volume (excluding the hollow core).

number

[0169] To calculate the total shell volume, the total polymer matrix volume and the total shell void volume were summed together. To determine the volume of the hollow core of the structure (bubble), the total shell volume was subtracted from the total foam structure (dot) volume.

number

number

[0170] The shell porosity of the structure (cell) was taken as the ratio of the total shell void volume to the total shell volume as a percentage. The foam structure (dot) porosity of the cell (including hollow core) was taken as the ratio of the sum of the total shell void volume and the hollow core volume to the total foam structure (dot) volume as a percentage.

number

number

[0171] Water solubility: The samples were subjected to a water solubility test to quantify the percentage of recoverable content. The samples were cut into two test pieces, each approximately 5.1 cm x 5.1 cm (2 inches x 2 inches), and the weight of each test piece was measured and recorded. The test piece of each sample was then placed in a covered glass jar containing 500 g of deionized (DI) water and heated and agitated in a heated shaker water bath (Aqua Pro Linear Shaker Bath available from Grant Instruments, Beaver Falls, PA, USA) operating at 55.5°C (130°F) and 100 strokes per minute. The samples were monitored for up to 6 hours, recording the time that had elapsed until the printed features were visibly peeled off the paper substrate. After the heat soak, the glass jar was removed from the shaker and the paper substrate was removed with tweezers and allowed to air dry. The contents of the glass jar were drained and filtered through a stainless steel wire cloth with 0.5 mm (0.02 in) opening and 57% open area (McMaster-Carr, Elmhurst, IL, USA) to remove excess water, then dried in an oven at 70° C. for 30 minutes (min). The dried remaining contents were then weighed and the % recoverable contents from water dissolution was calculated as follows:

number

[0172] Abrasion resistance: Testing was performed using a Model 5750 Linear Abrasion Tester (Taber Industries, North Tonawanda, NY, USA) according to ASTM D4060 Standard Test Method for Abrasion Resistance of Organic Coatings by the Taber Abraser using a flat, smooth stainless steel attachment. The instrument had a free-floating horizontal arm that moved back and forth in a linear motion, and a vertical splined shaft was attached to the horizontal arm, allowing a load to be applied to the shaft. For each experiment, the specimens were cut into strips approximately 5.08 cm x 20.32 cm (2 in x 8 in). Each specimen was secured to a mounting plate at the bottom of the splined shaft so that the 3 cm x 3 cm x 3 cm stainless steel attachment was in contact with the face of the specimen containing the patterned foam element. The mounting plate was set so that the stainless steel attachment was in contact with the patterned foam element at a 5° angle. The test was carried out with one weight disc attached to the shaft, which corresponds to a total weight of 600 g applied to the specimen from above. Each specimen is subjected to 60 cycles of abrasion at a speed of 1 cycle / second for the arm movement of the horizontal abrasion tester. Fresh specimens were used for each abrasion experiment, and the weight of the specimen as well as the weight of the uncoated paper substrate specimen were measured before and after the abrasion experiment to calculate the loss in percent as follows:

number

[0173] The precision of the test was determined according to the guidelines of ASTM D4060 and the standard deviation of the specimens tested.

[0174] Buffer properties: Foam cushioning properties were evaluated using the procedures outlined in ASTM D1696-14, Dynamic Impact Cushioning Properties, except as otherwise noted in this procedure. 2) test specimens were cut from sheets of foam coated substrate. The Lansmont cushion curve tester consists of a drop frame, a platen with a series of weights, a speedometer, an accelerometer, a DAC (digital to analog converter), and a computer with TP3 (Test Partner version 3) software. It is designed to measure the deceleration of a known mass impacting a cushioning material at a known velocity. The drop weight used for this test was 6.2 lbs, with a psi of 0.096 lbs / in 2 The drop height used was 6 inches and the impact velocity was measured for each drop. The deviation from the ASTM test method was that the initial foam height and the foam height after the test were recorded using hand calipers along the edge of the foam sheet. The average G (g force) deceleration of the three samples is recorded for drop #1 and drop #5. The percent change in G deceleration was calculated by dividing the G of the fifth drop by the G of the first drop. The percent change was reported. The initial foam height was also reported, as well as the foam height after the fifth drop. The percent reduction in foam height was calculated by dividing the foam height after the fifth drop by the initial height and reported as the percent change.

[0175] Seam Strength: The seam strength of sealed foam-padded mailing envelopes was determined using the procedure outlined in ASTM F88 / F88M, “Standard Test Method for Seal Strength of Flexible Barrier Materials.” Specimens 2.5 cm (1 in) wide were cut perpendicular to the seam from the sealed mailing envelopes with at least 5.1 cm (2 in) of material on either side of the seam. Prior to testing, the specimens were conditioned overnight in a temperature and humidity controlled room at 22.8 ± 1.1 °C (73.1 ± 2 °F) and 50 ± 2% relative humidity. Specimens were loaded into a constant rate of extension tensile testing machine (MTS ALLIANCE RT / 50 TESTING MACHINE, Eden Prairie, MN, USA) with a 1000 N load cell with an initial jaw separation of 3.8 cm (1.5 in). Using an extension rate of 25 cm / min (10 in / min), the samples were pulled until the seam separated and the average peak load, average load, and total energy of six specimens per sample were recorded. The seam width was measured and the seam strength was calculated by dividing the peak load by the seam width. The peak force was reported as lbs / in, the average force was reported as lbs / in, and the total energy was reported as lbf-in.

[0176] Friction Coefficient Test The static and kinetic coefficients of friction of the discrete foamed cell coated on paper were determined using the procedure outlined in ASTM D1894-14 "Standard Test Method for Static and Kinetic Coefficients of Friction of Plastic Film and Sheeting". The test setup was according to setup C (moving sled - fixed flat surface) described in ASTM 1894-14 using an Instron Coefficient of Friction Tester part number 2810-005 (available from Instron, Norwood MA, USA) using a 100N load cell and tested on an Instron Universal Testing Load Frame 5564 (available from Instron, Norwood MA, USA). The specimens were tested against steel plates having either a mirror or matte finish. Prior to testing, the steel plates were wiped with 70 / 30 isopropyl alcohol / water. Prior to testing, the specimens were conditioned overnight in a temperature and humidity controlled room at 22.8±1.1°C (73.1±2°F) and 50±2% relative humidity. Specimens were cut to the appropriate dimensions as outlined in ASTM and attached to a moving sled. The sled weight was 200g±5g including the attached specimen. Specimens were tested using a crosshead speed of 6 inches / minute. Samples were tested in triplicate. The kinetic and static coefficient of friction values ​​were recorded and average values ​​were reported.

[0177] Sample preparation procedure [Table 2] [Table 3] [Table 4]

[0178] Preparation of the Foamable Composition The formulations of the foamable compositions are summarized in Tables 2, 3, and 4 above. Generally, the raw materials are liquids, pellets, or powders. For solutions in which the polymer resins (RM3 and 4) are liquids, the final solutions can be prepared in a single step, and an exemplary solution procedure is shown below as Formulation 54. For solutions in which the polymer resins (RM1, 2, 5, 6, and 7) arrived as solids, the polymer resins were dissolved in water and / or IPA before preparing the final solutions. The concentrations of the polymer solutions made were determined in Tables 2, 3, and 4 by the provided amounts of polymer resins (RM1, 2, 5, 6, and 7) and the amount of water (RM31) or organic solvent (RM32) added in the formulation. The preparation of Formulation 57 is provided below as a general representative example of all mixtures in which the polymer resin arrived as a solid.

[0179] Formulation 54 Procedure: 1.6 kg of Joncryl HPB 4030 (RM4) was placed in a 1 gallon jar. 51.1 g of Expancel 043DU80 (RM11), 9.8 g of Methocel K4M (RM22), and 6.6 g of Colorant 32N711 (RM22) were placed in a 1 gallon jar. The solution was mixed for 30 minutes using a mechanical stirring cowl blade. The solution was allowed to sit for at least 24 hours before use.

[0180] Formulation 57 Procedure: One kilogram (1 kg) of G Polymer (RM1) was dissolved in 3 kg of deionized water under mechanical stirring to prepare an aqueous dispersion with 25% solids by weight. 1.77 kg of the 25% solids G Polymer solution was placed in a 1 gallon jar. This was followed by 0.443 kg of Dur-O-Set E130 (RM3), 58.7 g of Expancel 043DU80 (RM11), and 8.2 g of colorant 32N711. The solution was mixed for 30 minutes using a mechanical stirring cowl blade.

[0181] Rotogravure printing of foamable composition, medium air bubbles The following examples illustrate the rotogravure printing of a foamable composition to form a plurality of foam cells having a foamed exterior shell and a hollow air-filled interior, as best seen in Figures 16, 18, and 19. Tables 15 and 16 list the rotogravure roll patterns tested and additional materials used in the foamable composition. Tables 17-22 provide the wet and dry weights of the foamable composition for various examples.

[0182] In a rotogravure coating process such as that shown in FIG. 9, the foamable composition was deposited on the substrate in an array of liquid dots. In some embodiments, a substantially continuous coating was also used, applied to the substrate first or simultaneously with the array of liquid dots. See, for example, the rotogravure roll shown in FIG. 11 for an example of a double coating in a single pass. In one embodiment, a 55 lb (88.3 gsm) Kraft paper substrate was used. The diameter and height of the dots varied as a function of the coating process parameters and the particular rotogravure pattern utilized, including the individual cell volumes within the pattern. In one embodiment, the rotogravure cells forming the array of liquid dots were about half of a 4 mm diameter sphere, meaning the cell depth was 1.5 mm, or about half of a 1 mm diameter sphere, meaning the cell depth was 0.5 mm. In certain embodiments, the depth aspect ratio of the cell diameter to the cell depth was 1-10, or 1-5, or 1-3. For example, patterned roll F had a cell depth of 1.5 mm and a cell diameter of 8 mm, and patterned roll H had a cell depth of 1.5 mm and a cell diameter of 12 mm. The aspect ratio of the cell diameter to depth controlled the diameter, height, and basis weight of the deposited dots. The depth aspect ratio of roll H was 8, the depth aspect ratio of roll F was 5.33, and the aspect ratio of roll D was 2.67.

[0183] In various embodiments, the cell volume is between 0.2 and 500 mm 3 , or 0.2 to 250 mm 3 , or preferably 0.2 to 100 mm 3, or 1 to 20 mm 3 The cell volume is much larger compared to a typical rotogravure press since the foam structures tend to be large for the desired cushioning.

[0184] The rotogravure printing process shown in Figure 9 illustrates a method of making a packaging material. The method includes unwinding a roll of sheet material, passing the sheet material through a rotogravure station, printing a foamable composition on a first major surface of the sheet material using a rotogravure roll to form a coated sheet material, passing the coated sheet material through a drying oven, and foaming the foamable composition into a plurality of foam structures each having a hollow core and a foam exterior shell. After drying, the packaging material can be wound into a roll by a winder.

[0185] A suitable rotogravure roll or sleeve 180 is shown in Figures 11, 13, and 20. A variety of patterns can be placed on the circumference of the roll. In particular, a pattern having diagonal rotogravure cells can be used, as shown in Figure 20. Each cell has a length and a width, as viewed from top to bottom. The length can be significantly longer than the width, resulting in an aspect ratio in plan view of 10:1 to 1:1. The length of the cells is disposed at an angle α relative to the longitudinal axis 181 of the roll as viewed. The angle α can be any angle between 0 degrees and 180 degrees, for example, 35 degrees to 55 degrees, and in one embodiment was 45 degrees.

[0186] The deposited liquid dots were dried in an oven and foamed during the drying process to create a foam cell that includes an outer shell of foam material and a hollow center or core filled with air. The outer shell also attaches the foam cell to the sheet material. This means that the structure has a layer of sheet material followed by a layer of foamable composition located between the sheet material and the hollow center contiguous therewith, and also forms an exposed outer shell, followed by a hollow center portion, followed finally by an outer foam layer of the shell, as best seen in the cross-sectional views of Figures 18 and 19.

[0187] During drying, it is believed that the foamable composition, the outer skin above in the oven, and residual water in the composition at least partially evaporates into the center of the dot structure and exits through the substrate, creating the final hollow core structure seen in Figures 18 and 19. In particular, it has been found that slowing the web speed through the oven after the rotogravure printing process on the substrate is necessary for the formation of the skin layer and maximum hollow core volume within the foam cells.

[0188] Hollow foam cell structures have the advantage of creating a larger overall structure for a given amount of deposited foamable composition than can be obtained with non-hollow or solid core foam structures where the foam layer extends completely throughout the structure attached to the sheet material. Because they have an air-filled center, the final dried foam material is concentrated and utilized only in the outer shell of the structure. The resulting foam-coated overall substrate is very similar to a renewable version of plastic (polyethylene) bubble wrap. It has the pleasant calculated feel and good cushioning properties that come from the hollow air-filled core of the foam cells, just like plastic bubble wrap.

[0189] The formulation of Example 51 was used to prepare the padded foam sheet of Example 101. A roll of Kraft paper substrate was placed on the unwinder shown in Figure 10. The paper was fed to the rotogravure station and the drive nip was closed. An electric motor was used to regulate the web speed of the paper substrate to about 2.4 meters per minute (m / min, 8 ft / min) as it was fed to the rotogravure station. The coated paper was passed through an oven set at 350°F (182°C). The oven residence time was 60 seconds. Hot air was passed over the printed web by a manifold through eight nozzles measuring 15.5 inches wide by 0.375 inches. The distance from the nozzle tip to the paper was 2.5 to 3 inches. The velocity of the air exiting the nozzles ranged from 4 m / s to 9 m / s as measured by a digital rotary vane anemometer (Omega HHF5000, 25 mm diameter probe) placed 1 inch from the nozzle exit. The preferred air velocity is 7 m / s at 350° F. with a residence time in the length of the dryer of 60 seconds. At an air velocity of 15 m / s and a temperature of 500° F., a residence time of 10 seconds can be used. The maximum temperature and time can be a function of the melt temperature of the polymers in the composition.

[0190] The foamable composition was deposited on a roll of 55 lb. Kraft paper by rotogravure with a 3D printed gravure sleeve. The sleeve was printed with ABS filament and a layer height of 0.007 inches on a Stratasys F370 FDM printer. The printed sleeve, measuring 7.62 cm ID x 10.3 cm OD x 35.5 cm long, was attached to a 7.6 cm diameter shaft to form a gravure roll 180. The sleeve was printed to form hemispherical cells on the outer surface with dimensions of 4 mm diameter x 1.5 mm deep with 2 mm spacing between adjacent cells. The sleeve attached to the shaft was placed in a rotogravure station and the foamable composition was printed. The roll pattern is listed in Table 5 as gravure pattern D.

[0191] An unexpected benefit of the 3D printed gravure roll was that the 3D printing process left circumferential ridges and valleys on the surface of the roll, as seen in Figures 11 and 13. Metal machined gravure rolls are normally perfectly smooth in the land areas between the large circular holes that form the discrete elements. Thus, in addition to the foamable composition printing of the discrete foam elements, the surface of the substrate was also printed with closely spaced lines that create a continuous foam coating layer on the substrate. The continuous foam layer significantly increases the seam strength of heat sealed packaging articles such as mailers and envelopes, and is believed to enhance the durability of the discrete foam elements by more firmly anchoring them to the substrate. Examples created within this disclosure utilized a 3D printed rotogravure patterned roll that was then lightly sanded to remove the continuous printing between the foam bubbles.

[0192] The resulting foam coating using the gravure roll of Figure 13 on a substrate is shown in Figures 12A and 12B. As seen in Figure 12B, the printed lines from the 3D printed gravure roll appear as faint lines in the continuous coating layer between the discrete elements. The continuous coating layer ends near the edge of the substrate 10 leaving uncoated areas 19, in this case where only the kraft paper surface is present. The foamable composition in this embodiment was dyed to match the color of the kraft paper for more visual appeal.

[0193] The basis weight range of the continuous foam coating can be 0-50 gsm, 5-30 gsm, or 5-20 gsm. The basis weight range of the discontinuous discrete foam elements can be 5-100 gsm, 10-80 gsm, or 15-70 gsm. The total coating weight is the sum of the previous individual ranges.

[0194] Referring to FIG. 11, a gravure roll having both discrete circular elements 185 and a plurality of microgrooves 187 is used to illustrate the concept of printing a foamable composition onto a substrate to form a continuous foam coating. The discrete elements were formed by large circular apertures arranged in a parallelogram pattern that placed the discrete elements in a row of lines angled relative to the edge of the substrate. A continuous coating layer was laid down by circumferential grooves in the land area of ​​the roll between the apertures. This was achieved by 3D printing closely spaced circumferential lines or filaments onto the roll surface. The composition foamed after application, so laying down the foamable composition in discrete lines formed a substantially continuous coating on the substrate as the composition foamed. Rather than 3D printing a gravure roll, machined rolls with similar features could also be constructed.

[0195] The gravure roll coating technique allowed for a continuous foam coating between the discrete foam elements. This continuous coating provided a continuous heat sealable layer over the entire surface. This continuous coating substantially increased the seam seal strength when heat sealed. The foam coated substrate with the continuous foam layer and the discrete foam elements can be formed into any of the packaging articles shown in Figures 2, 3, 4, 5, 6, or 7 and the above discussion on how to make them. It is particularly suitable for forming envelopes with heat sealed seams and sealing flaps, such as an envelope with three heat sealed seams forming an inner pouch and a sealing flap closure as shown in Figures 11A-11C. These packages are often called mailers and are used to transport products from online retailers to customers.

[0196] Dyes or pigments can be added to the foamable composition to match the color of the foam to the color of the Kraft paper it is coated with. The colored coating creates a good color match between the discrete elements, and the continuous coating layer and the Kraft paper results in a visually appealing article. In some embodiments, the concentration of the dye ranged from 0.01% to 5.0% by weight. [Table 5] [Table 6] [Table 7]

[0197] result The coating weights and overall sample thicknesses of the foam padded materials are provided in Table 8. To calculate the coating weight, the basis weight of the Kraft paper was assumed to be 88.3 gsm. The combined thickness of the foam and paper was measured using a simple caliper, with the uncoated Kraft paper having a thickness of 0.14 mm (5.5 mils). A number of solution cast polymer systems were evaluated. Surprisingly, it was determined that hollow core porous shell structures could be produced with multiple chemistries coated from solution at appropriate solution viscosities with preferred viscosities ranging from 1000 cP to 15,000 cP. Significantly below this viscosity range, discrete dots of solution below 500 cP were not properly deposited, instead a continuous coating without dots of solution was obtained. Higher viscosity solutions presented challenges with handling the solution during coating, but dots could be transferred.

[0198] The examples shown in Table 8 with a hollow core percent of total cell volume, such as Example 106 (11%), Example 117 (35%), and Example 120 (30%), surprisingly had a total porosity of over 50% as shown by X-ray tomography. This was surprising since it was expected that the total porosity would be determined primarily by the hollow core volume. The results show that the total porosity was determined by the hollow core volume, the shell porosity, and the shell thickness. [Table 8]

[0199] Table 8 shows the optical microscopy characterization for samples 101-126. The examples disclosed in Table 8 were spherical bubbles. Characterization data included bubble diameter, bubble height, bubble volume, hollow core volume, and hollow core volume percent of total bubble volume. Table 8 shows the results for the hollow core volume of 0.2 mm 3 ~100mm 3 The results show that the percent of hollow core volume out of the total cell volume ranged from 11 to 99%. The shell thickness ranged from 0.044mm to 0.94mm. The basis weight of these samples ranged from 7.9 up to 79.6gsm. The basis weight was affected by the size and density of the dots deposited on the substrate. The % solids of the solution also affected the basis weight of the foam material.

[0200] Table 9 shows the characterization of Examples 127-133, which are rectangular in shape, and the length, width, height, and shell thickness were measured to calculate the cell volume, hollow core volume, and hollow core volume percent. The basis weight of the rectangular shaped foam bubble coating deposited on the substrate ranged from 109 gsm to 148 gsm. This was increased or decreased outside of these values ​​by simply increasing or decreasing the size of the bubbles, i.e., the amount of material deposited in a given area, by changing the cell depth of the rotogravure pattern or by changing the density of the foam pattern for a given area. The height of the foam dots ranged from 1.4 to 3.0 mm. The bubble volume after foaming ranged from 39 to 211 mm. 3 The hollow core volume is in the range of 21 to 175 mm 3 The percentage of cells formed that were hollow core comprised 53% to 87% of the total cell volume. The shell thickness ranged from 0.12 mm to 0.32 mm. [Table 9]

[0201] Table 10 shows the X-ray tomography characterization of the foam cells. X-ray tomography is a method that generates a 3-dimensional imaged volume from 2-dimensional X-ray image slices. This allows for accurate characterization of the total foam cell porosity. X-ray tomography allowed for accurate characterization of the total cell volume and hollow core volume, as did optical microscopy. In addition, X-ray tomography was able to characterize the porosity of the foam cell shell as well. Combining all three allowed for accurate characterization of the total foam dot porosity to be determined. The X-ray tomography characterization shown in Table 10 allowed for accurate characterization of the total foam dot porosity, as shown in Table 10, for a 0.7 mm 3 ~125.7mm 3 Total bubble volume in the range of 0.21mm 3 ~56.3mm 3Hollow core volumes ranging from 1 mm to 50 mm, shell porosities ranging from 71.5% to 82.4%, and total foam cell porosities ranging from 79.2% to 88.0% are disclosed. Surprisingly, varying the overall cell volume of the foam cells did not dramatically affect the total porosity of the structure. Thus, cell sizes can be increased to within 1 mm while maintaining a porosity of over 50%. 3 From very small, less than 125mm 3 These range from very large to very large. [Table 10]

[0202] Table 11 shows the comparison of the total void volume to the hollow core volume, as well as the percentage of the total void volume that is hollow core. The values ​​between the two methods agreed fairly well. If the shell porosity needs to be measured, X-ray tomography should be used. If only the hollow core volume and the foam structure volume need to be measured, a person skilled in the art of measurement science can choose whichever method (optical microscopy or X-ray tomography) that gives reasonable results. Foam structures with regular shapes, such as circles or rectangles, may be suitable for optical measurements, while structures with irregular shapes may require X-ray tomography.

[0203] The combination of the two methods showed that in examples with a low hollow core volume percentage, for example Example 106 where the hollow core volume constitutes only 10.8%-13.5%, depending on the method, the total porosity of the bubbles is actually 79.2%. The porous shell had a large impact on the overall porosity of the foam dots. In various embodiments of the present invention, the shell porosity can be 50%-95%, or 60%-90%, or 65%-85%.

[0204] Theoretically, and with the formulation ranges provided, in samples where the hollow core constituted only a small portion of the total cell volume, e.g., less than 10%, the total porosity of the cells still exceeded 50% porosity. The porosity of the shell was controlled by the type and loading of microspheres in the composition and the process conditions used to dry and expand the microspheres. [Table 11]

[0205] The results of the abrasion resistance test are summarized in Table 12 and were used to evaluate the durability of the foam coating samples. The samples suffered up to about 50% mass loss after abrasion due to the foam composition being shredded after repeated abrasion. Thus, the abrasion resistance of the packaging material can be less than 50%, 40%, 35%, 30%, 20%, or 10%. [Table 12]

[0206] Table 13 discloses the results of the seam strength of the sheet material. The seam strength value was important to develop sufficient strength of the heat sealed edge of the packaging article to avoid the need to use an adhesive layer to seal the seam. In this disclosure, the foam material served as a cushioning layer as well as a heat sealable layer that created the packaging article edge. Generally, seam strength with a peak force value of at least 1.0 lbs / in is considered acceptable, with peak force values ​​of at least 1.5 lbs / in, or at least 2.0 lbs / in, or at least 3.0 lbs / in being preferred. The sealing temperature and dwell time were varied to increase or decrease the seam strength value. The reported values ​​were taken at 350°F with a seal time of 0.8 seconds. It was found that increasing the temperature or dwell time increased the seam strength value. The reported seam strength values ​​ranged from 0 lbs / in for 105, where no heat seal was formed, to 4.5 lbs / in for 125, for example. The internal air bubbles and porous shell structure and polymer resin also affected the resulting seam strength values. The total energy required to peel open the heat sealed seam was also reported. These values ​​ranged from, for example, 0 lbf-in for Example 105 to, for example, 1.15 lbf-in for Example 113.

[0207] The flexibility of the present invention allowed for the modification of the chemistry, cell shape, size, and aspect ratio of the central air bubble porous shell to be easily tailored to the required foam properties. For example, in Examples 101-107, the polymer chemistry of the base resin, which generally constitutes more than 85% of the total composition, is varied. By varying the base chemistry of the polymer resin, the peak seal strength and the total energy to peel the seam were changed by a factor of more than 10x.

[0208] In certain embodiments, foam structures cast from solutions utilizing polymer chemistries that result in hollow core and porous shell structures had seam strengths with a peak force of at least 1.0 lbs / in, more preferably at least 1.5 lbs / in, and most preferably at least 2.0 lbs / in. In other embodiments, foam structures cast from solutions utilizing polymer chemistries that result in hollow core and porous shell structures had seam strengths that required a total energy of at least 0.5 lbf-in, more preferably 0.75 lbf-in, and most preferably 1.0 lbf-in to peel the seam open.

[0209] The flexibility of the present invention allowed for optimization of the porous shell by selecting the type and loading of expandable microspheres used to create the porous shell. There is a range of expandable microspheres that allow both initial and final microsphere sizes to be selected, and the expansion onset temperature can be varied to suit specific processing conditions. These important microsphere properties influenced the shell thickness and overall shell integrity, as well as the hollow core volume, when the expansion onset temperature was close to the boiling point of the solvent. Examples 108-111 illustrate this effect. By selecting the correct microsphere type for a given set of process conditions, in this case 350F for 60 seconds, microspheres with a high activation temperature, such as those shown in Example 111, resulted in shells with smaller pores, reduced shell porosity, and better shell integrity, which corresponds to a higher seam seal strength peak force.

[0210] In certain embodiments, the pore size within the foam shell after coating and drying of the foam material ranges from 10 to 250 microns, more preferably from 20 to 200 microns, more preferably the pore size is from 40 to 180 microns, and most preferably from 60 to 160 microns.

[0211] The microsphere loading percentage of the dried foam composition also had a significant effect on the ultimate strength of the heat sealed seam. Examples 112-115 show this effect for EXPANCEL 043DU80 (RM11), and Examples 116-119 show this effect for DUALITE U010-130D (RM12). Both series show microsphere loadings ranging from about 1% to about 12% of the total foam composition after drying. Surprisingly, the effect of microsphere loading on seam strength was not linear in nature. The data in Examples 112-115 show that the preferred range of microsphere loading was near 4% of the total composition after drying. Lower or higher amounts of microspheres reduce the peak force and total energy required to peel the seam. This was surprising in light of the fact that those skilled in the art tend to think that simply increasing the microsphere content dilutes the polymer resin volume that ultimately creates the heat seal. Therefore, the lowest microsphere loadings would be expected to have the highest seam strength, as shown in Examples 116-119. This factor was taken into consideration when balancing all other properties required for a suitable packaging article.

[0212] In certain embodiments, the preferred microsphere loading is 1-12% by weight of the total composition, preferably the microsphere loading is up to 8% by weight of the total dry composition, and most preferably the microsphere loading is 0.1-5% by weight of the total dry composition.

[0213] The pattern selected for coating the foam on the substrate also had a significant effect on the seam strength. This was observed in many of the examples provided in Table 13, but a few were highlighted. Comparing Examples 110 and 111 to 124 and 125, it can be seen that by increasing the bubble size and decreasing the space between the dots, superior seam strength was obtained. These effects are also seen in the dot diameter of the resulting foam structure in Table 8, where for a given system, wider dots promoted higher seam strength. The amount of overlap between the foam dots on opposing surfaces during heat sealing provided the best opportunity for an ideal heat seal. In addition, the pattern selected affected the bubble height, and when compared to the same system with the same foam bubble diameter and the only difference being the height, such as Example 121 (Formulation 51 coated with Patterned Roll H) compared to Example 123 (Formulation 51 with Patterned Roll F), the measured dot diameter was nearly identical at 6.5 mm ± 0.1 mm, but the dot height was substantially different. Example 121 had a bubble height of 2.6 mm and Example 123 had a height of 3.5 mm. Surprisingly, Example 123 had almost 50% higher seam strength than Example 121.

[0214] In certain embodiments, the foam cells have a diameter in the range of 1 mm to 7 mm, or 1 mm to 3 mm, or more preferably 3 mm to 7 mm. In other embodiments, the cell height is in the range of 0.6 mm to 3.8 mm, or at least 0.6 mm, or at least 2 mm, more preferably in the range of 1.5 mm to 4 mm.

[0215] The examples show that this is a complex system of polymer chemistry, formulation parameters including % solids, raw material type and loading, coating pattern, and process conditions that affect the degree of expansion and ultimately the size of the hollow core and porosity in the shell. All of these variables have interactions that affect the foam material properties, and the requirements for a given application may prioritize one property over another. In addition, the seam strength values ​​are for a given set of sealing conditions. Increasing the temperature, dwell time, or pressure can significantly increase the seam strength value. Finally, the selection of the substrate can improve seam strength if the compatibility of the substrate with the foaming resin is improved. Heat seal strength can be further improved by improving substrate polymer compatibility via additives embedded or coated in the paper, or by selecting a film or nonwoven that is more compatible with the selected foam composition. [Table 13]

[0216] The cushioning properties of the hollow core porous shell foam structures were evaluated using ASTM D1696-14, "Dynamic Shock Cushioning Characteristics." This ASTM was designed to generate cushioning curves, typically involving a large series of weights dropped from a series of heights, to fully understand the cushioning properties, a summary of which is disclosed within this application. Table 14 shows the results for the 6" to 64" drop curves. 2 The figures show the deceleration of a platen with a weight equal to 6.2 lbs (0.096 psi) dropped onto a foam substrate of 100 mm. The pressure selected was appropriate for object weights and sizes typical of the packaging articles described within this application. G is reported in Table 14. 1 g = 9.8 m / s on the ground 2 It is known to those skilled in the art of cushioning curve testing that for items shipped in the packaging articles described in this application, the typical G(g's) that the items can undergo without being destroyed approached 1000 g.

[0217] The platen G deceleration for the first and fifth drops, the % change in G deceleration between drop 1 and drop 5, and the % decrease in foam thickness were reported for a series of samples. Under the specific test parameters described in the Test Methods section, the reported G deceleration for the fifth drop ranged from 451 g to 165 g. It is believed that increasing the amount of microspheres can increase the cushioning behavior. For Examples 113-115, this was true. However, by simply changing the grade of microspheres while keeping the rest of the system the same as in Examples 108-111, the opposite trend is realized. In Examples 108-111, it was confirmed that as the grade of microspheres was changed, the thickness of the porous shell increased with decreasing microsphere loading, and that for this particular grade, the best combination of cushioning with the least amount of foam height change or cushioning behavior change occurred in Example 110.

[0218] By examining Tables 8, 10 and 14 in detail, it was determined that the total cell volume and core volume can affect cushioning behavior, as seen in Examples 117-119.

[0219] In certain embodiments, the foams with hollow core and porous shell have cushioning properties of less than 150G, less than 250G, or less than 350G when tested as described. In other embodiments, the foams with hollow core and porous shell have cushioning properties in the range of 150G to 350G, or at least 150G. In certain embodiments, the foams with hollow core and porous shell have a reduction in height from the initial height, ranging from 5% to 95%. It is preferred that the foam not lose too much height, as this may affect the cushioning properties of subsequent drops. In certain embodiments, it is preferred to have foams with hollow core and porous shell that exhibit a foam height reduction of 0 to 50%, more preferably 0 to 25%, and most preferably 0 to 15% after the fifth drop. [Table 14]

[0220] For foam substrates formed into mailers, a lower coefficient of friction is desirable for inserting items into the mailer and moving the foam substrate through a processing line. In preferred embodiments, the kinetic COF can be less than 2.0, or less than 1.5, or less than 1.0, and greater than 0.0. Table 15 shows the coefficient of friction data obtained for select foam samples. One of the unique properties of the present invention is the amount of freedom that the hollow core and porous shell structure gives to manipulate the overall material properties. The data shows that the COF properties can be controlled by the polymer chemistry of the foam cells, as well as the shape and size of the foam structure. These properties can be controlled by the formulation, the patterned coating roll design, the orientation of the pattern if it is not symmetric in the downweb and crossweb directions (e.g. rectangular shape), and the process conditions during drying. The ability to tune the properties through the pattern is compared in Examples 127 and 131. Both examples have the same pattern with rectangular features 12 mm long by 2 mm wide. The difference is that Example 127 has a 12 mm dimension running across the web (cross machine direction) while Example 131 has a dimension running downweb (machine direction). This simple change in orientation reduces the dynamic COF value by over 10%.

[0221] In certain embodiments, the foam substrate has a kinetic COF of friction less than 0.2, less than 0.4, less than 0.6, or less than 1.0. In certain embodiments, the foam substrate has a kinetic coefficient of friction less than 2.0, less than 1.5, less than 1.0, or less than 0.5. In some embodiments, the kinetic coefficient of friction ranges from 0.3 to 1.0, more preferably from 0.3 to 0.8. [Table 15]

[0222] Various modifications and alterations to this disclosure will become apparent to those skilled in the art without departing from the scope and spirit of the disclosure. It is to be understood that this disclosure is not intended to be unduly limited by the exemplary embodiments and examples described herein, and that such examples and embodiments are presented only as examples within the scope of this disclosure, which is intended to be limited only by the claims set forth herein as follows. All references cited in this disclosure are incorporated herein by reference in their entirety.

Claims

1. 1. A packaging material comprising: a first sheet material; a plurality of foam structures formed from a foamable composition, attached to the sheet material by a layer of the foamable composition, each foam structure having a hollow core and a foam exterior shell; a total porosity of said plurality of foam structures is determined by X-ray microtomography by adding a hollow core volume to an outer shell void volume, then dividing the sum by the foam structure volume and multiplying by 100, said total porosity being greater than 50% and less than 100%.

2. The packaging material of claim 1 , wherein the plurality of foam structures comprises a plurality of dots.

3. 2. The packaging material of claim 1, wherein the first sheet material has a first major surface and an opposing second major surface, and the plurality of foam structures are present on both the first major surface and the second major surface.

4. 2. The packaging material of claim 1, comprising a second sheet material facing the first sheet material, the plurality of foam structures being disposed between the first sheet material and the second sheet material.

5. 10. The packaging material of claim 1, wherein the foamable composition comprises at least one polymer component selected from the group consisting of butanediol vinyl alcohol polymer or copolymer, starch, vinyl acetate / ethylene copolymer, polyvinyl acetate, polyvinyl alcohol, dextrin stabilized polyvinyl acetate, vinyl alcohol / vinyl acetate copolymer, vinyl alcohol / vinyl acetate / ethylene copolymer, stabilized polyvinyl acrylate copolymer, vinyl (meth)acrylic, styrene (meth)acrylic, (meth)acrylic, styrene butyl rubber, natural rubber, styrene block copolymer, polyurethane, polyethylene oxide, polyvinylpyrrolidone, and mixtures thereof.

6. 10. The packaging material of claim 1, wherein the foamable composition comprises at least one polymer component further comprising polyvinyl alcohol stabilized vinyl acetate ethylene (VAE).

7. The packaging material of claim 1 , wherein the foamable composition comprises water.

8. 10. The packaging material of claim 1, wherein the foamable composition comprises expandable microspheres having an initial expansion temperature greater than 100°C.

9. 10. The packaging material of claim 1, wherein the foamable composition further comprises one or more optional additives selected from the group consisting of tackifiers, plasticizers, nucleating agents, colorants, reinforcing agents, solid fillers, rheology modifiers, toughening agents, thickeners, flame retardants, preservatives, antioxidants, defoamers, crosslinkers, waxes, stabilizers, wetting agents, accelerators, antistatic agents, slip agents, release additives, LABs, and combinations thereof.

10. 1. A packaging material comprising: a first sheet material; a plurality of foam structures formed from a foamable composition, attached to the sheet material by a layer of the foamable composition, each foam structure having a hollow core and a foam exterior shell; A packaging material, wherein a hollow core volume percent is determined by dividing the hollow core volume by the foam structure volume and multiplying by 100, said hollow core volume percent being greater than 15% and less than 95%.

11. The hollow core volume is 5 mm 3 ~100mm 3 The packaging material according to claim 10,

12. 1. A method of making a packaging material, comprising: unwinding a roll of sheet material; passing the sheet material through a rotogravure station to print a foamable composition onto a first major surface of the sheet material to form a coated sheet material; passing the coated sheet material through a drying oven to expand the foamable composition into a plurality of foam structures each having a hollow core and a foam exterior shell.

13. The rotogravure station includes a rotogravure roll having a plurality of cells disposed on an outer roll circumference, the plurality of cells each having a diameter of 0.2 mm or less. 3 ~100mm 3 The method of claim 12 having a cell volume of

14. The method of claim 12 or 13, wherein the rotogravure station comprises a rotogravure roll having a plurality of cells, the aspect ratio of the cell diameter divided by the cell depth being between 1 and 10.

15. 13. The method of claim 12, wherein the rotogravure station includes a rotogravure roll having a plurality of cells disposed on an outer roll circumference, the plurality of cells having a rectangular shape.